Accelerated partial breast irradiation using sole interstitial multicatheter brachytherapy compared with whole-breast irradiation with boost for early breast cancer: 10-year results of a GEC-ESTRO randomised, phase 3, non-inferiority trial - Strnad, Vratislav; Polgár, Csaba; Ott, Oliver; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Łyczek, Jarosław; Guinot, Jose Luis; Gutierrez Miguelez, Cristina; Slampa, Pavel; Allgäuer, Michael; et al. (The Lancet. Oncology, 2023)
BACKGROUND: Several randomised, phase 3 trials have investigated the value of different techniques of accelerated partial breast irradiation (APBI) for patients with early breast cancer after breast-conserving surgery compared with whole-breast irradiation. In a phase 3 randomised trial, we evaluated whether APBI using multicatheter brachytherapy is non-inferior compared with whole-breast irradiation. Here, we present the 10-year follow-up results. METHODS: We did a randomised, phase 3, non-inferiority trial at 16 hospitals and medical centres in Austria, Czech Republic, Germany, Hungary, Poland, Spain, and Switzerland. Patients aged 40 years or older with early invasive breast cancer or ductal carcinoma in situ treated with breast-conserving surgery were centrally randomly assigned (1:1) to receive either whole-breast irradiation or APBI using multicatheter brachytherapy. Whole-breast irradiation was delivered in 25 daily fractions of 50 Gy over 5 weeks, with a supplemental boost of 10 Gy to the tumour bed, and APBI was delivered as 30·1 Gy (seven fractions) and 32·0 Gy (eight fractions) of high-dose-rate brachytherapy in 5 days or as 50 Gy of pulsed-dose-rate brachytherapy over 5 treatment days. Neither patients nor investigators were masked to treatment allocation. The primary endpoint was ipsilateral local recurrence, analysed in the as-treated population; the non-inferiority margin for the recurrence rate difference (defined for 5-year results) was 3 percentage points. The trial is registered with ClinicalTrials.gov, NCT00402519; the trial is complete. FINDINGS: Between April 20, 2004, and July 30, 2009, 1328 female patients were randomly assigned to whole breast irradiation (n=673) or APBI (n=655), of whom 551 in the whole-breast irradiation group and 633 in the APBI group were eligible for analysis. At a median follow-up of 10·36 years (IQR 9·12-11·28), the 10-year local recurrence rates were 1·58% (95% CI 0·37 to 2·8) in the whole-breast irradiation group and 3·51% (1·99 to 5·03) in the APBI group. The difference in 10-year rates between the groups was 1·93% (95% CI -0·018 to 3·87; p=0·074). Adverse events were mostly grade 1 and 2, in 234 (60%) of 393 participants in the whole-breast irradiation group and 314 (67%) of 470 participants in the APBI group, at 7·5-year or 10-year follow-up, or both. Patients in the APBI group had a significantly lower incidence of treatment-related grade 3 late side-effects than those in the whole-breast irradiation group (17 [4%] of 393 for whole-breast irradiation vs seven [1%] of 470 for APBI; p=0·021; at 7·5-year or 10-year follow-up, or both). At 10 years, the most common type of grade 3 adverse event in both treatment groups was fibrosis (six [2%] of 313 patients for whole-breast irradiation and three [1%] of 375 patients for APBI, p=0·56). No grade 4 adverse events or treatment-related deaths have been observed. INTERPRETATION: Postoperative APBI using multicatheter brachytherapy after breast-conserving surgery in patients with early breast cancer is a valuable alternative to whole-breast irradiation in terms of treatment efficacy and is associated with fewer late side-effects. FUNDING: German Cancer Aid, Germany.
CRIS-Team Scopus Importer:2023-03-10

A Delphi study and International Consensus Recommendations: The use of bolus in the setting of postmastectomy radiation therapy for early breast cancer - Kaidar-Person, Orit; Dahn, Hannah M.; Nichol, Alan M.; Boersma, Liesbeth J.; de Ruysscher, Dirk; Meattini, Icro; Pignol, Jean Philippe; Aristei, Cynthia; Belkacemi, Yazid; Benjamin, Dori; Bese, Nuran; Coles, Charlotte E.; et al. (Radiotherapy and Oncology, 2021)
Bolus serves as a tissue equivalent material that shifts the 95–100% isodose line towards the skin and subcutaneous tissue. The need for bolus for all breast cancer patients planned for postmastectomy radiation therapy (PMRT) has been questioned. The work was initiated by the faculty of the European SocieTy for Radiotherapy & Oncology (ESTRO) breast cancer courses and represents a multidisciplinary international breast cancer expert collaboration to optimize PMRT. Due to the lack of randomised trials evaluating the benefits of bolus, we designed a stepwise project to evaluate the existing evidence about the use of bolus in the setting of PMRT to achieve an international consensus for the indications of bolus in PMRT, based on the Delphi method.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Bolus; Breast cancer; Mastectomy; PMRT; Radiation therapy; Tissue compensator

Assessment of needle bending and tracking requirements for optimized needle placement in combined intracavitary/interstitial gynecologic brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Merten, Ricarda; Fietkau, Rainer; Bert, Christoph; Schweizer, Claudia (Strahlentherapie und Onkologie, 2025)
Purpose: Needle tracking using external prediction techniques such as optical tracking is a modern approach aimed at improving implantation accuracy in gynecologic brachytherapy. This study aims to investigate the corresponding impact of needle bending in situ and to analyze needle path deviations from the intended locations occurring in our current clinical workflow that only considers ultrasound imaging without tracking. Methods: We developed a semi-automated approach for reconstructing brachytherapy needles based on planning CTs and compared the respective accuracy to the also determined intra-observer variability of manual reconstructions. Based on this, we measured needle bending in situ for 89 patients and calculated the Euclidean distances between actual needle tips and needle tip predictions both longitudinally and laterally to the insertion direction. Furthermore, we compared actual and intended spacings between inserted needles to estimate implantation uncertainties with respect to our current clinical workflow. Results: Our developed reconstruction featured an accuracy of 0.17 ± 0.08 mm, which was improved compared to the intra-observer variability of 0.21 ± 0.11 mm. Needle bending depended strongly on needle length and ranged from 3.6 ± 2.1 mm for 100–120 mm needles up to 7.9 ± 3.0 mm for 200–220 mm needles. Deflections in the transverse direction were substantially higher than tip deviations in the longitudinal direction. Furthermore, we found deviations from an equidistant spacing between needle paths of 1.4 ± 1.2 mm in the transverse direction. Conclusion: Inserting brachytherapy needles can be substantially affected by transverse needle bending in situ, which should therefore be corrected for in prediction approaches such as optical tracking.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Adaptive brachytherapy; Image guidance; Intraoperative navigation; Needle displacement; Optical infrared tracking

Automating implant reconstruction in interstitial brachytherapy of the breast: A hybrid approach combining electromagnetic tracking and image segmentation - Dürrbeck, Christopher; Sauer, Birte; Lotter, Michael; Kreppner, Stephan; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2022)
Background and purpose: To develop a method for automatic reconstruction of catheter implants in interstitial brachytherapy (iBT) of the breast by means of electromagnetic tracking (EMT) with the goal of making treatment planning as time-effective and accurate as possible. Materials and methods: The implant geometry of 64 patients was recorded using an afterloader prototype with EMT functionality immediately after the planning CT. EMT data were transferred to the CT image space by rigidly registering the catheter fixation buttons as landmarks. To further improve reconstruction accuracy, the EMT reconstruction points were used as starting points to define small regions of interest (ROI) in the CT image. Within these ROIs, the catheter track was segmented in the CT using image processing operations such as thresholding and blob detection, thus refining the reconstruction. The perpendicular distance between the refined EMT implant reconstruction points and the manually reconstructed catheters by an experienced treatment planner was calculated as a measure of their geometric agreement. Results: Geometrically, the refined EMT based implant reconstruction shows excellent agreement with the manual reconstruction. The median distance across all patients is 0.25 mm and the 95th percentile is 1 mm. Refinement takes approximately 0.5 s per reconstruction point and typically does not exceed 3 min per implant at no user interaction. Conclusion: The refined EMT based implant reconstruction proved to be extremely accurate and fast compared to manual reconstruction. The presented procedure can in principle be easily transferred to clinical routine and therefore has enormous potential to provide significant time savings in iBT treatment planning whilst improving reconstruction accuracy.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Breast cancer; Electromagnetic tracking; Implant reconstruction; Interstitial brachytherapy

Automation of Implant Reconstruction in Interstitial Brachytherapy of the Breast Using Electromagnetic Tracking - Dürrbeck, Christopher; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (MEDICAL PHYSICS, 2022)
CRIS-Team WoS Importer:2022-07-08

Automatisation of catheter reconstruction in interstitial breast BT using electromagnetic tracking - Dürrbeck, Christopher; Abu-Hossin, N.; Lotter, M.; Kreppner, Stephan; Lubgan, Dorota; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-15

Brachytherapy boost in anal canal cancer – A GEC ESTRO PDR task force meta-analysis - Annede, Pierre; Ferre, Marjorie; Kirisits, Christian; Pieters, Bradley R.; Schmid, Maximilian; Strnad, Vratislav; Westerveld, Henrike; Chargari, Cyrus (Clinical and Translational Radiation Oncology, 2023)
Purpose: A meta-analysis is presented comparing clinical outcomes and toxicities between high dose rate (HDR) and pulsed dose rate (PDR) brachytherapy (BT) for anal cancer. Methods and material: Retrospective or prospective clinical trials were identified on electronical databases. Data were collected per Preferred Reporting Items for Systematic Reviews and meta-Analyses guidelines. Pooled effect size for HDR and PDR BT were compared using subgroup analyses. Results: Nine retrospective studies with a total of 481 patients treated were included of which 219 with HDR and 262 with PDR. Significant differences were observed between the two groups for baseline characteristics and treatment. The cumulative proportion of stage T3-T4 was lower in the HDR group, 0.15 [95 % confidence interval (CI) 0.07–0.29] vs 0.27 [95 %CI 0.09–0.57] in the LDR group, p < 0.001. Lower BT doses (in equivalent 2-Gy fraction dose) were given for patients in the HDR group, 11.9 Gy [95 %CI 8.2–15.5] vs 19.5 Gy [95 %CI 15.0–24.0] in the PDR group, p < 0.001. No significant differences were found for clinical outcomes or toxicities. The pooled effect size of the overall survival at 5 years for HDR and PDR was respectively 0.82 [95 %CI 0.70–0.94] and 0.82 [95 %CI 0.73–0.91], p > 0.99. The 5 years local control was 0.86 [95 % confidence interval (CI) 0.81–0.91] and 0.83 [95 %CI 0.77–0.89], p = 0.62. Cumulative toxicity-related colostomy proportion was 0.04 [95 %CI 0.02–0.09] and 0.03 [95 %CI 0.02–0.07], p = 0.85. Conclusion: Both modalities provided a good profile of tolerance and are effective organ conservative strategies for patients with anal canal cancer. In parallel with ongoing developments to better determine the optimal fractionation and dose for HDR-BT treatments, especially in large tumors, PDR BT still has a crucial role for dose escalation strategy in advanced cases.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Anal cancer; Brachytherapy; High-dose rate brachytherapy; Local control; Morbidity; Pulsed-dose rate brachytherapy; Toxicity

Brachytherapy focal dose escalation using ultrasound based tissue characterization by patients with non-metastatic prostate cancer: Five-year results from single-center phase 2 trial - Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer (Brachytherapy, 2022)
PURPOSE: This prospective trial investigates side effects and efficacy of focal dose escalation with brachytherapy for patients with prostate cancer. METHODS AND MATERIALS: In the Phase II, monocentric prospective trial 101 patients with low-/intermediate- and high-risk prostate cancer were enrolled between 2011 and 2013. Patients received either PDR-/HDR-brachytherapy alone with 86–90 Gy (EQD2, α/β = 3 Gy) or PDR-/HDR-brachytherapy as boost after external beam radiation therapy up to a total dose of 91–96 Gy (EQD2, α/β = 3 Gy). Taking place brachytherapy all patients received the simultaneous integrated focal boost to the intra-prostatic tumor lesions visible in computer-aided ultrasonography (HistoScanning™) - up to a total dose of 108–119 Gy (EQD2, α/β = 3 Gy). The primary endpoint was toxicity. Secondary endpoints were cumulative freedom from local recurrence, PSA-free survival, distant metastases-free survival, and overall survival. This trial is registered with ClinicalTrials.gov, number NCT01409876. Results: Median follow-up was 65 months. Late toxicity was generally low with only four patients scoring urinary grade 3 toxicity (4/101, 4%). Occurrence of any grade of late rectal toxicities was very low. We did not register any grade ≥2 of late rectal toxicities. The cumulative 5 years local recurrence rate (LRR) for all patients was 1%. Five years- biochemical disease-free survival estimates according Kaplan-Meier were 98,1% and 81,3% for low-/intermediate-risk and high-risk patients, respectively. Five years metastases-free survival estimates according Kaplan-Meier were 98,0% and 83,3% for all patients, low-/intermediate-risk and high-risk patients, respectively. Conclusions: The 5 years-results from this Phase II Trial show that focal dose escalation with computer-aided ultrasonography and brachytherapy for patients with non-metastatic prostate cancer is safe and effective.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Brachytherapy; Focal dose escalation; Prostate cancer

Brachytherapy in vaginal cancer for organ preservation: Clinical outcome and safety from a single center experience - Merten, Ricarda; Strnad, Vratislav; Karius, Andre; Lotter, Michael; Kreppner, Stephan; Schweizer, Claudia; Fietkau, Rainer; Schubert, Philipp (Gynecologic Oncology, 2024)
Background: Interstitial and/or intracavitary brachytherapy is an integral part of the treatment of vaginal cancer Brachytherapy (BT) has shown to improve local control, overall survival (OS) and disease-free survival (DFS). The aim of our study was to analyze the efficacy and safety of brachytherapy in patients with vaginal cancer. Materials and methods: Between 2000 and 2023, 27 patients with vaginal cancer in stage FIGO I-III were treated with brachytherapy with or without external beam radiotherapy (EBRT) and simultaneous chemotherapy. Brachytherapy has been performed either as PDR-brachytherapy alone with a median cumulative dose up to 62.5 Gy (EQD2 = 63.9 Gy) or with PDR-BT boost with median dose of 30.9 Gy (EQD2 = 30.4 Gy). HDR-BT was administered solely as boost with a median dose of 25.5 Gy (EQD2 = 47.8 Gy). The median dose of EBRT was 48.7 Gy and 49.4 Gy for primary and for pelvic lymph nodes. Results: Median follow-up was 39 months (2−120). 5/27 patients developed local recurrences and the 5-year cumulative local recurrence rate for whole patient population was 18.5%. 5-year OS and DFS was 90% and 68%. 5-year DFS for Stage I-II was 72% and for Stage III 65% (p = 0.933). Grade 3 late side effects of brachytherapy were documented in 3/22 patients (13.6%), one patient experienced Grade 4 toxicity (4.5%). Conclusion: Brachytherapy with or without EBRT and concomitant chemotherapy for vaginal cancer is a safe and effective treatment option with excellent local control and overall survival and acceptable toxicity.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Brachytherapy; Dose-escalation; Organ-sparing; Vaginal cancer

Brachytherapy training survey among radiation oncology residents in Europe - Sturdza, Alina Emiliana; Stephanides, Marianne; Jurgenliemk-Schulz, Ina; Eriksen, Jesper Grau; Benstead, Kim; Hoskin, Peter; Vlad, Stefanel; Escande, Alexandre; Corradini, Stefanie; Knoth, Johannes; Westerveld, Henrike; Tagliaferri, Luca; et al. (Radiotherapy and Oncology, 2022)
We aim to investigate the current state of brachytherapy (BT) training among the radiation oncology trainees in Europe. Material and methods: A 22-question online survey based on the one by the American Association of Radiation Oncology Residents (2017) with added queries pertinent to training in Europe was sent to 1450 residents in two iterations. These included site-specific training, volume of experience, barriers to training, institutional support, and preferences for further education. Responses to individual statements were given on a 1 to 5 Likert-type scale. The answers were reported by junior (≤3 years of training) and senior years of training (year of training 4/5/6 and junior staff). Descriptive statistics were used to describe frequencies. Results: Residents from 21 European countries participated, 445 (31%) responded. 205 (47%) were senior residents. 60% residents consider that performing BT independently at the end of residency is very or somewhat important. Confidence in joining a brachytherapy practice at the end of residency was high or somewhat high in 34% of senior residents. They reported as barriers to achieving independence in BT to be lack of appropriate didactic/procedural training from supervisors (47%) and decreased case load (31%). 68% reported their program lacks a formal BT curriculum and standardized training assessment. Conclusions: Residents in Europe, feel independent BT practice is very or somewhat important, but do not feel confident they will achieve this goal. To address this gap, efforts are needed to develop and implement a formal and comprehensive BT curriculum with easy access to trained instructors.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Brachytherapy training; Education; Radiation oncology residents

Comparison of dose calculation approaches and clinical dose–response in image-guided head&neck brachytherapy of the oral cavity - Schaller, Sabrina; Strnad, Vratislav; Schweizer, Claudia; Lubgan, Dorota; Merten, Ricarda; Fietkau, Rainer; Bert, Christoph; Karius, Andre (Clinical and Translational Radiation Oncology, 2025)
Purpose: Model-based dose calculation algorithms (MBDCAs) are increasingly applied in brachytherapy, but their considerations in dose–response analyses is still lacking. This study aimed to assess correlations between both TG-43 and MBDCA dosimetry and reports on clinical outcomes for oral cavity brachytherapy. Methods: We considered 158 patients with oral cavity cancer treated in our institution between 2012 and 2021. Survival outcomes and toxicity (soft tissue necrosis, osteoradionecrosis, mucositis, xerostomia) were reported for a median follow-up of 80 months (2–152 months). All clinical, TG-43 based treatment plans were re-calculated using a MBDCA integrated into our planning system. Differences considering several target volume, tissue, and bone dose parameters were evaluated. Parameter correlations with clinical outcomes and thresholds associated with increased toxicity were investigated. Results: Cumulative local recurrence, soft-tissue necrosis, osteoradionecrosis, mucositis, and xerostomia rate were 21 %, 22 %, 28 % and 79 % considering all patients. Substantial differences between MBDCA and TG-43 were observed, especially regarding high-dose areas with changes up to 19 %. A number of dose-toxicity correlations were observed, as for osteoradionecrosis (1.6 % vs. 10.3 % for bone D2ccm ≥ 59.3 Gy), soft tissue necrosis (16 % vs. 32 % for tissue D5ccm ≥ 87.7 Gy), and local recurrence (13 % vs. 25 % for dose non-uniformity ratio < 0.29) (using the MBDCA). Target volumes ≥ 10.2–11.8ccm were associated with increased rates of soft tissue necrosis and mucositis. Dosimetric thresholds and correlations differed between TG-43 and MBDCA. Conclusion: For oral cavity brachytherapy, several important dosimetric thresholds associated with increased toxicity were determined. MBDCAs for corresponding dose calculations should be advanced and used in clinical practice.
CRIS-Team Scopus Importer:2025-05-16

Cone-beam CT imaging with laterally enlarged field of view based on independently movable source and detector - Karius, Andre; Szkitsak, Juliane; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: CBCT imaging with field of views (FOVs) exceeding the size of scans acquired in the conventional imaging geometry, i.e. with opposing source and detector, is of high clinical importance for many medical fields. A novel approach for enlarged FOV scanning with one full-scan (EnFOV360) or two short-scans (EnFOV180) using an O-arm system arises from non-isocentric imaging based on independent source and detector rotations. Purpose: The presentation, description, and experimental validation of this novel approach and the novel scanning techniques EnFOV360 and EnFOV180 for an O-arm system forms the scope of this work. Methods: We describe the EnFOV360, EnFOV180, and non-isocentric imaging techniques for the acquisition of laterally extended FOVs. For their experimental validation, scans of dedicated quality assurance as well as anthropomorphic phantoms were acquired, with the phantoms being placed both within the tomographic plane and at the longitudinal FOV border with and without lateral shifts from the gantry center. Based on this, geometric accuracy, contrast-noise-ratio (CNR) of different materials, spatial resolution, noise characteristics, as well as CT number profiles were quantitatively assessed. Results were compared to scans performed with the conventional imaging geometry. Results: With EnFOV360 and EnFOV180, we increased the in-plane size of acquired FOVs from 250 × 250 mm2 obtained for the conventional imaging geometry to up to 400 × 400 mm2 for the performed measurements. Geometric accuracy was very high for all scanning techniques with mean values ≤0.21 ± 0.11 mm. CNR and spatial resolution were comparable between isocentric and non-isocentric full-scans as well as EnFOV360, whereas substantial image quality deteriorations in this respect were observed for EnFOV180. Image noise in the isocenter was lowest for conventional full-scans with 13.4 ± 0.2 HU. For laterally shifted phantom positions, noise increased for conventional scans and EnFOV360, whereas noise reductions were observed for EnFOV180. Considering the anthropomorphic phantom scans, both EnFOV360 and EnFOV180 were comparable to conventional full-scans. Conclusion: Both enlarged FOV techniques have high potential for imaging laterally extended FOVs. EnFOV360 revealed an image quality comparable to conventional full-scans in general. EnFOV180 showed an inferior performance particularly regarding CNR and spatial resolution.
CRIS-Team Scopus Importer:2023-05-26
Keywords: cone-beam computed tomography; extended field of view; independent gantry rotations

Definitive treatment for primary urethral cancer: A single institution's experience with organ-preserving brachytherapy - Merten, Ricarda; Strnad, Vratislav; Karius, Andre; Lotter, M.; Kreppner, Stephan; Schweizer, Claudia; Fietkau, Rainer; Schubert, Philipp (Brachytherapy, 2024)
BACKGROUND: Radical urethectomy ± cystectomy has long represented the standard of care for rare primary urethral cancer (PUC). With our analysis, we want to demonstrate the efficacy and safety of brachytherapy (BT) of urethra for organ preservation. MATERIALS AND METHODS: We analyzed treatment procedures and results of 3 patients with PUC, which have been treated in our department between 2011 and 2020 with brachytherapy. One male patient underwent brachytherapy with chemoradiotherapy after transurethral resection (TUR). Brachytherapy has been performed as high-dose-rate (HDR) boost with a cumulative dose of 8 Gy (9.3 Gy EQD2-α/β = 10 Gy). The 2 further female patients have been treated with sole pulsed-dose-rate (PDR) brachytherapy with a total dose of 49.9 Gy (50.3 Gy EQD2-α/β = 10 Gy) and 62.2 Gy (64.6 Gy EQD2-α/β = 10 Gy). RESULTS: Median follow-up was 103 months (41–153). No local recurrence occurred and all patients are still alive. For the male patient we documented Grade 3 cystitis. As late side effects the pre-existing Grade 2 incontinence worsened to Grade 3. Among female patients one developed Grade 3 vaginal synechiae. There was no Grade ≥4 toxicity. CONCLUSION: Brachytherapy in PUC is a feasible and promising option with high local control rate and tolerable toxicity. It provides a good alternative to surgery for organ preservation in selected patients.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Brachytherapy; Dose-escalation; Organ-preservation; Primary urethral cancer

DEGRO guideline for personalized radiotherapy of brain metastases and leptomeningeal carcinomatosis in patients with breast cancer - Borm, Kai J.; Behzadi, Sophie T.; Hörner-Rieber, Juliane; Krug, David; Baumann, Rene; Corradini, Stefanie; Duma, Marciana Nona; Dunst, Jürgen; Fastner, Gerd; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; et al. (Strahlentherapie und Onkologie, 2024)
Purpose: The aim of this review was to evaluate the existing evidence for radiotherapy for brain metastases in breast cancer patients and provide recommendations for the use of radiotherapy for brain metastases and leptomeningeal carcinomatosis. Materials and methods: For the current review, a PubMed search was conducted including articles from 01/1985 to 05/2023. The search was performed using the following terms: (brain metastases OR leptomeningeal carcinomatosis) AND (breast cancer OR breast) AND (radiotherapy OR ablative radiotherapy OR radiosurgery OR stereotactic OR radiation). Conclusion and recommendations: Despite the fact that the biological subtype of breast cancer influences both the occurrence and relapse patterns of breast cancer brain metastases (BCBM), for most scenarios, no specific recommendations regarding radiotherapy can be made based on the existing evidence. For a limited number of BCBM (1–4), stereotactic radiosurgery (SRS) or fractionated stereotactic radiotherapy (SRT) is generally recommended irrespective of molecular subtype and concurrent/planned systemic therapy. In patients with 5–10 oligo-brain metastases, these techniques can also be conditionally recommended. For multiple, especially symptomatic BCBM, whole-brain radiotherapy (WBRT), if possible with hippocampal sparing, is recommended. In cases of multiple asymptomatic BCBM (≥ 5), if SRS/SRT is not feasible or in disseminated brain metastases (> 10), postponing WBRT with early reassessment and reevaluation of local treatment options (8–12 weeks) may be discussed if a HER2/Neu-targeting systemic therapy with significant response rates in the central nervous system (CNS) is being used. In symptomatic leptomeningeal carcinomatosis, local radiotherapy (WBRT or local spinal irradiation) should be performed in addition to systemic therapy. In patients with disseminated leptomeningeal carcinomatosis in good clinical condition and with only limited or stable extra-CNS disease, craniospinal irradiation (CSI) may be considered. Data regarding the toxicity of combining systemic therapies with cranial and spinal radiotherapy are sparse. Therefore, no clear recommendations can be given, and each case should be discussed individually in an interdisciplinary setting.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Craniospinal irradiation; Molecular profile; Neurocognitive side effects; Radiosurgery; Whole-brain radiotherapy

Development of Recurrence and Long-term Toxicity in Prostate Carcinoma after combined Radiotherapy with interstitial Brachytherapy Boost - Schweizer, Claudia; Strnad, Vratislav; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Dose volume histogram constraints in patients with soft tissue sarcomas of the extremities and the superficial trunk treated with surgery and perioperative HDR brachytherapy: Dose Volume Histogram Constraints for Sarcoma Brachytherapy - Gómez-Álvarez, Jorge; Martín Pastor, Santiago; Gimeno, Marta; Lamo-Espinosa, José; Ramos, Luis I.; Cambeiro, Mauricio; Tagliaferri, Luca; Kovacs, Gyoergy; Strnad, Vratislav; San-Julián, Mikel; Martinez-Monge, Rafael (Radiotherapy and Oncology, 2022)
Background: Wound healing complications (WHC), osteoradionecrosis (ORN), and nerve damage (ND) are common adverse effects in adult patients with soft tissue sarcomas of the extremities and the superficial trunk treated with surgery and perioperative high dose rate brachytherapy (PHDRB) alone or combined with external beam radiotherapy (EBRT). Rationale: Analysis of the treatment factors contributing to these complications can potentially minimize their occurrence and severity. Patients: A total of 169 patients enrolled in two parallel prospective studies were included in this analysis. Previously Unirradiated cases (Group 1; n = 139) were treated with surgical resection, 16–24 Gy of PHDRB and 45 Gy of EBRT. Adjuvant chemotherapy was given to selected patients with high-grade tumors. Previously irradiated cases (Group 2; n = 30) were treated with surgical resection and 32–40 Gy of PHDRB without further EBRT. Methods: Patient factors, tumor factors, surgical factors, PHDRB factors and EBRT factors were analyzed using Cox univariate and multivariate analysis. Results: In Previously Unirradiated cases, WHC, ORN and ND occurred in 38.8%, 5.0% and 19.4%. Multivariate analysis indicated that WHC increased with CTV size (p = 0.02) and CTV2cm3 Physical dose (p = 0.02). ORN increased with Bone2cm3 EQD2 ≥ 67 Gy (p = 0.01) and ND was more frequent in patients with TV100 DVH-based dose (tissue volume encompassed by the 100% isodose) ≥ 84 Gy (p < 0.01). In Previously Irradiated cases, WHC, ORN and ND occurred in 63.3%, 3.3% and 23.3%. Multivariate analysis showed that WHC was more frequent in patients with Skin2cm3 Lifetime EQD2 ≥ 84 Gy (p = 0.01) and ND was more frequent after CTVD90 Physical Doses ≥ 40 Gy (p < 0.01). Conclusions: WHC in Previously Unirradiated patients can be minimized by using a more conservative CTV definition together with a meticulous implant technique and planning aimed to minimize hyperdose CTV2cm3 areas. In Previously Irradiated patients WHC may be mimimized considering Lifetime EQD2 Skin2cm3 doses. ORN can be reduced by using the Bone2cm3 EQD2 constraint. ND occurs more frequently in patients with large tumors receiving high treated volume doses, but no specific constraints can be recommended due to the lack of peripheral nerve definition during brachytherapy planning.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Brachytherapy; External Beam Radiation Therapy; High Dose Rate; Late complications; Perioperative; Soft tissue sarcomas

Endocrine therapy with accelerated Partial breast irradiatiOn or exclusive ultra-accelerated Partial breast irradiation for women aged >= 60 years with Early-stage breast cancer (EPOPE): The rationale for a GEC-ESTRO randomized phase III-controlled trial - Hannoun-Levi, Jean-Michel; Chamorey, Emmanuel; Boulahssass, Rabia; Polgar, Csaba; Strnad, Vratislav (Clinical and Translational Radiation Oncology, 2021)
Purpose: Breast cancer in the elderly has become a public health concern; there is a need to re-design its treatment with a view to de-escalation. Our paper sets out the rationale for a phase 3 randomized trial to evaluate less burdensome adjuvant procedures that remain effective and efficient.
CRIS-Team WoS Importer:2021-07-16

Establishing an intraoperative, mobile CBCT-based workflow for gynecologic brachytherapy: primary experience and benefit assessment - Karius, Andre; Strnad, Vratislav; Bert, Christoph; Fietkau, Rainer; Merten, Ricarda; Schweizer, Claudia (Frontiers in Oncology, 2025)
Background and purpose: In the brachytherapy of cervical cancer, creating a suitable implant based on ultrasound guidance may be impacted by imaging limitations. To validate the implant if ultrasound is not sufficient, we implemented a new workflow utilizing additional intraoperative cone-beam computed tomography (CBCT). The aims of this work were to describe the newly established workflow, reflect associated (dis)advantages, and assess geometric and dosimetric benefits compared to the previous solely ultrasound-guided workflow. Materials and methods: We report the establishment of our new workflow utilizing mobile CBCT during interventions and corresponding experiences for 26 consecutive patients. Image quality was assessed by considering the applicator visualization and contrast–noise ratio (CNR) between tissues. Implant changes based on CBCT scans were analyzed with respect to the enhanced insertion depths (EIDs) of needles and their tip distances to target volume borders. Dosimetric effects were evaluated by calculating common dose–volume parameters for target volume and organs at risk (OARs) and comparing them in both a previous patient cohort and scenarios simulating sole ultrasound guidance. Implant uncertainties between intra- and postoperative imaging were analyzed using a corresponding registration as well. Results: Implementing intraoperative CBCT was associated with clinical challenges but increased safety feeling during interventions and resulted in geometric as well as dosimetric benefits. Needles could be shifted deeper into the pelvis by an EID of 14 ± 11 mm based on CBCT, associated with corresponding significant dose improvements for target volume and OARs with a mean tradeoff increase of up to 4.8 Gy. With a reasonable CNR between tissues up to 8.5 ± 3.6 and clear detectability of applicators, image quality was sufficient to fulfill intraoperative intentions. Furthermore, the CBCT scans were suitable for treatment planning purposes from a geometric uncertainty perspective. Conclusion: The implementation of intraoperative CBCT can substantially improve the quality and safety of image-guided gynecologic brachytherapy.
CRIS-Team Scopus Importer:2025-05-09
Keywords: adaptive brachytherapy; image-guidance; interventional radiotherapy; intraoperative imaging; mobile CT

Estimating follow-up CTs from geometric deformations of catheter implants in interstitial breast brachytherapy: A feasibility study using electromagnetic tracking - Dürrbeck, Christopher; Schulz, Moritz; Pflaum, Leonie; Kallis, Karoline; Geimer, Tobias; Abu-Hossin, Nadin; Strnad, Vratislav; Maier, Andreas; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: Electromagnetic tracking (EMT) systems have been shown to provide valuable information on the geometry of catheter implants in breast cancer patients undergoing interstitial brachytherapy (iBT). In the context of an extended patient-specific, pre-treatment verification, EMT can play a key role in determining the potential need and, if applicable, the appropriate time for treatment adaptation. To detect dosimetric shortcomings the relative position between catheters, and target volume and critical structures must be known. Since EMT cannot provide the anatomical context and standard imaging techniques such as cone-beam CT are not yet available in most brachytherapy suites, it is not possible to detect anatomic changes on a daily or fraction basis, so the need for adaptive planning cannot be identified. Purpose: The aim of this feasibility study is to develop and evaluate a technique capable of estimating follow-up CTs at any time based on the initial treatment planning CT (PCT) and surrogate information about changes of the implant geometry from an EMT system. Methods: A deformation vector field is calculated from two different implant reconstructions acquired in treatment position through EMT, the first immediately after the PCT and the second at another time point during the course of treatment. The calculation is based on discrete displacement vectors of pairs of control and target points. These are extrapolated by means of different radial basis functions in order to cover the entire CT volume. The adequate parameters for the calculation of the deformation field were identified. By warping the PCT according to the deformation field, one obtains an estimated CT (ECT) that reflects the geometric changes. For the proof of concept, ECTs were computed for the time point of the clinical follow-up CT (FCT) that is embedded in the treatment workflow after the fourth fraction. Results: ECT and clinical FCTs of 20 patients were compared to each other quantitatively in terms of absolute Hounsfield unit differences in the planning target volume (PTV) and in a convex hull (CH) enclosing the catheters. The median differences were 31.2 and 29.5 HU for the CH and the PTV, respectively. Conclusion: The proposed ECT approach was able to approximate the “anatomy of the day” and therefore, in principle, allows a dosimetric appraisal of the treatment plan quality before each fraction. In this way, it can contribute to a more detailed patient-specific quality assurance in iBT of the breast and help to identify the timing for a potential treatment adaptation.
CRIS-Team Scopus Importer:2023-08-25
Keywords: assurance; breast cancer; electromagnetic tracking; interstitial brachytherapy

External Beam Accelerated Partial Breast Irradiation in Early Breast Cancer and the Risk for Radiogenic Pneumonitis - Ott, Oliver; Stillkrieg, Wilhelm; Lambrecht, Ulrike; Sauer, Tim-Oliver; Schweizer, Claudia; Lamrani, Allison; Strnad, Vratislav; Hack, Carolin; Beckmann, Matthias; Uder, Michael; Fietkau, Rainer; Distel, Luitpold (Cancers, 2022)
Simple Summary Accelerated partial breast irradiation represents a well-established and safe treatment alternative for selected patients with early stage breast cancer after breast-conserving surgery. In a prospective trial on external beam partial breast irradiation, the risk for radiogenic pneumonitis is analyzed. After a median follow-up of 56 (1-129) months, radiogenic pneumonitis grade 2 appeared in only 1/170 (0.6%) patients. Compared to standard whole breast irradiation, the radiation doses applied to the lungs were very low. The patient with the radiogenic pneumonitis was found to have a generally increased radiation susceptibility. Using accelerated partial breast irradiation, the risk of radiogenic pneumonitis appeared quite low and may be limited to very exceptional cases associated with innate risk factors with an increased radiation susceptibility. In order to evaluate the risk for radiation-associated symptomatic pneumonitis in a prospective external beam accelerated partial breast irradiation (APBI) trial, between 2011 and 2021, 170 patients with early stage breast cancer were enclosed in the trial. Patients were eligible for study participation if they had a histologically confirmed breast cancer or an exclusive ductal carcinoma in situ (DCIS), a tumor size <= 3 cm, free safety margins >= 2 mm, no involved axillary lymph nodes, tumor bed clips, and were >= 50 years old. Patients received APBI with 38 Gy with 10 fractions in 10 consecutive working days. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Median follow-up was 56 (1-129) months. Ipsilateral lung MLD, V20, and V30 were 4.3 +/- 1.4 Gy, 3.0 +/- 2.0%, and 1.0 +/- 1.0%, respectively. Radiogenic pneumonitis grade 2 appeared in 1/170 (0.6%) patients two months after radiotherapy. Ipsilateral MLD, V20, and V30 were 6.1 Gy, 7, and 3% in this patient. Additionally, individual radiosensitivity was increased in this specific patient. Compared to WBI, APBI leads to lower lung doses. Using APBI, the risk of symptomatic radiogenic pneumonitis is very low and may be limited, with an ipsilateral V20 < 3% to very exceptional cases associated with innate risk factors with an increased radiation susceptibility.
CRIS-Team WoS Importer:2022-08-12

External-Beam-Accelerated Partial-Breast Irradiation Reduces Organ-at-Risk Doses Compared to Whole-Breast Irradiation after Breast-Conserving Surgery - Ott, Oliver; Stillkrieg, Willy; Lambrecht, Ulrike; Schweizer, Claudia; Lamrani, Allison; Sauer, Tim-Oliver; Strnad, Vratislav; Bert, Christoph; Hack, Carolin; Beckmann, Matthias; Fietkau, Rainer (Cancers, 2023)
In order to evaluate organ-at-risk (OAR) doses in external-beam-accelerated partial-breast irradiation (APBI) compared to standard whole-breast irradiation (WBI) after breast-conserving surgery. Between 2011 and 2021, 170 patients with early breast cancer received APBI within a prospective institutional single-arm trial. The prescribed dose to the planning treatment volume was 38 Gy in 10 fractions on 10 consecutive working days. OAR doses for the contralateral breast, the ipsilateral, contralateral, and whole lung, the whole heart, left ventricle (LV), and the left anterior descending coronary artery (LAD), and for the spinal cord and the skin were assessed and compared to a control group with real-world data from 116 patients who underwent WBI. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Compared to WBI, APBI led to reduced OAR doses for the contralateral breast (0.4 ± 0.6 vs. 0.8 ± 0.9 Gy, p = 0.000), the ipsilateral (4.3 ± 1.4 vs. 9.2 ± 2.5 Gy, p = 0.000) and whole mean lung dose (2.5 ± 0.8 vs. 4.9 ± 1.5 Gy, p = 0.000), the mean heart dose (1.6 ± 1.6 vs. 1.7 ± 1.4 Gy, p = 0.007), the LV V23 (0.1 ± 0.4 vs. 1.4 ± 2.6%, p < 0.001), the mean LAD dose (2.5 ± 3.4 vs. 4.8 ± 5.5 Gy, p < 0.001), the maximum spinal cord dose (1.5 ± 1.1 vs. 4.5 ± 5.7 Gy, p = 0.016), and the maximum skin dose (39.6 ± 1.8 vs. 49.1 ± 5.8 Gy, p = 0.000). APBI should be recommended to suitable patients to minimize the risk of secondary tumor induction and the incidence of consecutive major cardiac events.
CRIS-Team Scopus Importer:2023-08-25
Keywords: accelerated partial-breast irradiation; breast cancer; mean heart dose; mean lung dose; organs-at-risk

First clinical experience with a novel, mobile cone-beam CT system for treatment quality assurance in brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Bert, Christoph (Strahlentherapie und Onkologie, 2022)
Background and purpose: On-site cone-beam computed tomography (CBCT) has gained in importance in adaptive brachytherapy during recent years. Besides treatment planning, there is increased need particularly for image-guidance during interventional procedures and for image-guided treatment quality assurance (QA). For this purpose, an innovative CBCT device was rolled out at our hospital as the first site worldwide. We present the first clinical images and experiences. Materials and methods: The novel CBCT system is constructed of a 121 cm diameter ring gantry, and features a 43.2 × 43.2 cm2 flat-panel detector, wireless remote-control via tablet-PC, and battery-powered maneuverability. Within the first months of clinical operation, we performed CBCT-based treatment QA for a total of 26 patients (8 with breast, 16 with cervix, and 2 with vaginal cancer). CBCT scans were analyzed regarding potential movements of implanted applicators in-situ during the brachytherapy course. Results: With the presented device, treatment QA was feasible for the majority of patients. The CBCT scans of breast patients showed sufficient contrast between implanted catheters and tissue. For gynecologic patients, a distinct visualization of applicators was achieved in general. However, reasonable differentiations of organic soft tissues were not feasible. Conclusion: The CBCT system allowed basic treatment QA measures for breast and gynecologic patients. For image-guidance during interventional brachytherapy procedures, the current image quality is not adequate. Substantial performance enhancements are required for intraoperative image-guidance.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Adaptive brachytherapy; Gynecologic brachytherapy; Image-guidance; Mobile imaging; On-site computed tomography imaging

First implementation of an innovative infra-red camera system integrated into a mobile CBCT scanner for applicator tracking in brachytherapy—Initial performance characterization - Karius, Andre; Leifeld, Lisa Marie; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2024)
Purpose: To enable a real-time applicator guidance for brachytherapy, we used for the first time infra-red tracking cameras (OptiTrack, USA) integrated into a mobile cone-beam computed tomography (CBCT) scanner (medPhoton, Austria). We provide the first description of this prototype and its performance evaluation. Methods: We performed assessments of camera calibration and camera-CBCT registration using a geometric calibration phantom. For this purpose, we first evaluated the effects of intrinsic parameters such as camera temperature or gantry rotations on the tracked marker positions. Afterward, calibrations with various settings (sample number, field of view coverage, calibration directions, calibration distances, and lighting conditions) were performed to identify the requirements for achieving maximum tracking accuracy based on an in-house phantom. The corresponding effects on camera-CBCT registration were determined as well by comparing tracked marker positions to the positions determined via CBCT. Long-term stability was assessed by comparing tracking and a ground-truth on a weekly basis for 6 weeks. Results: Robust tracking with positional drifts of 0.02 ± 0.01 mm was feasible using the system after a warm-up period of 90 min. However, gantry rotations affected the tracking and led to inaccuracies of up to 0.70 mm. We identified that 4000 samples and full coverage were required to ensure a robust determination of marker positions and camera-CBCT registration with geometric deviations of 0.18 ± 0.03 mm and 0.42 ± 0.07 mm, respectively. Long-term stability showed deviations of more than two standard deviations from the initial calibration after 3 weeks. Conclusion: We implemented for the first time a standalone combined camera-CBCT system for tracking in brachytherapy. The system showed high potential for establishing corresponding workflows.
CRIS-Team Scopus Importer:2024-05-03
Keywords: brachytherapy; combined camera-CT system; infra-red applicator tracking; system characterization

Gastrointestinal Brachytherapy - Strnad, Vratislav (Brachytherapy, 2023)
Brachytherapy is a sophisticated and proven treatment technique of different GI localizations. Here the development of GI– brachytherapy of last 20 years, current position and the perspectives for next years are discussed. In summary: The GI–brachytherapy of different localizations is very effective, in experienced hands a safe technique and should be part of armamentarium of every radiation oncologist.
CRIS-Team Scopus Importer:2023-02-10

GEC-ESTRO recommendations for head & neck cancer brachytherapy (interventional radiotherapy): 2nd update with focus on HDR and PDR - Guinot, J. L.; Bacorro, W.; Budrukkar, A.; Bussu, F.; Gonzalez-Perez, V.; Jaberi, R.; Martinez-Monge, R.; Rembielak, A.; Rovirosa, A.; Strnad, Vratislav; Takácsi-Nagy, Z.; Tagliaferri, L. (Radiotherapy and Oncology, 2024)
Modern brachytherapy (BT) is playing an important role in the multidisciplinary treatment of Head and Neck (H&N) cancer, as an organ- and function-preserving therapy. Low-dose-rate (LDR) technology has been replaced by modern remote afterloading and stepping source equipment using pulsed dose rate (PDR) or high dose rate (HDR) sources, improved image guidance and 3D treatment planning systems. This is an update of the previous GEC-ESTRO recommendations for H&N tumors, mainly applied to squamous carcinomas. Indications, results and recommended doses for different tumor sites are presented according to the published studies.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Brachytherapy; HDR; Head and neck; Interventional radiotherapy; PDR; Recommendations

Guideline development GEC ESTRO - Strnad, Vratislav; Perez-Calatayud, J.; Jurgenliemk-Schulz, I. (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-26

Implant-based reconstruction and adjuvant radiotherapy in breast cancer patients—current status and DEGRO recommendations - Piroth, M. D.; Krug, D.; Baumann, R.; Strnad, Vratislav; Borm, K.; Combs, S.; Corradini, S.; Duma, M. N.; Dunst, J.; Fastner, G.; Feyer, P.; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2025)
Purpose: The aim of this review is to give an overview of the results of prospective and retrospective studies using allogenic reconstruction and postmastectomy radiotherapy (PMRT) in breast cancer and to make recommendations regarding this interdisciplinary approach. Materials and methods: A PubMed search was conducted to extract relevant articles from 2000 to 2024. The search was performed using the following terms: (breast cancer) AND (reconstruction OR implant OR expander) AND (radiotherapy OR radiation). Data from the literature on allogenic breast reconstruction and radiation are presented and discussed in relation to toxicity and cosmesis. Conclusion and recommendations: Breast reconstruction is also feasible if PMRT is necessary. Patients need to be informed about the relevant risk of capsular fibrosis and implant failure. A planned reconstruction is no reason to forgo PMRT nor is an indication for PMRT a reason to forego implant-based breast reconstruction if desired by the patient. It is important to provide detailed information here to enable shared decision-making. There is still no clear consensus regarding implant-based reconstruction (IBR) and PMRT. However, in clinical practice, both a one-stage (immediate “implant-direct” IBR) procedure with PMRT up to the final implant and a two-stage (immediate-delayed IBR) procedure with PMRT up to the tissue expander (TE) and later exchange of the TE are used; both approaches have their specific advantages and disadvantages. Depending on patient-specific factors and the surgeon’s experience and estimates, both IBR procedures are also possible in combination with PMRT. When using a TE/implant approach, completing skin stretching by adequately filling the expander before PMRT may be favorable. This approach is particularly practical when adjuvant chemotherapy is planned but may lead to postponement of radiotherapy when primary systemic therapy is given. According to the latest data, moderate hypofractionation also appears to be safe in the context of the IBR approach. It is important to have a closely coordinated interdisciplinary approach and to fully inform patients about the increased rate of potential side effects.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Breast cancer; Breast reconstruction; Implant-based reconstruction; Mastectomy; Postmastectomy radiotherapy; Radiotherapy

Influence and compensation of patient motion in electromagnetic tracking based quality assurance in interstitial brachytherapy of the breast - Dürrbeck, Christopher; Gulde, Sarah; Abu-Hossin, Nadin; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Medical Physics, 2022)
Purpose: Electromagnetic tracking (EMT) is a versatile and viable technique for various quality assurance (QA) tasks in interstitial brachytherapy (iBT). As the duration of EMT measurements in iBT is on the order of minutes, they can be strongly affected by patient motion, especially breathing, which gives rise to motion artefacts. Since the centrepiece of EMT-related QA in iBT is to assess the geometry of the iBT implant or applicator, the absence of adequate motion compensation techniques could impede the use of EMT for QA purposes. A common way to compensate for this is to reference the data to either external or internal reference sensors (ERS, IRS) which are fixated on the patient's body or inside the applicator and therefore move with the patient. The purpose of the presented study is to provide a quantitative and in-depth analysis on the use of reference sensors for motion compensation. Methods: First, the need for adequate motion compensation is identified both qualitatively and quantitatively using a phantom subjected to simulated breathing motion. An evaluation routine is developed to assess the influence of motion compensation using reference sensors on the acquired EMT data. The evaluation metric is based on the observed displacement of the EMT sensor from its mean position while dwelling at a dwell position (DP) for a dwell time of 1 s. After that, the routine is applied to a cohort of 54 breast cancer patients treated with iBT, and the quality of an ERS based compensation approach is assessed. In a subgroup of four patients, an IRS is inserted into the iBT implant and IRS-based compensation is compared to the ERS-based approach. Moreover, a correlation analysis of the ERS and IRS approach is performed, also including respiratory signals derived from the trajectories of the different reference sensors. Results: It was found that motion compensation with ERS effectively reduced the mean sensor displacement per DP to median values as low as 0.11 mm in both phantom and patient measurements, which is below the precision of the EMT system (0.48 mm). Compensation using the IRS yielded comparable results and was as good as compensation with ERS. The results obtained from both approaches showed a strong correlation. Also the respiratory signals calculated from the different reference sensors were well correlated in most cases. Conclusion: These results indicate that motion compensation with ERS can effectively remove motion artefacts in EMT data. While compensation with an IRS leads to comparable results, the IRS occupies one catheter whose geometry hence cannot be assessed. The use of ERS has proven to be both effective and practical in clinical routine.
CRIS-Team Scopus Importer:2022-03-04
Keywords: breast cancer; breathing motion; electromagnetic tracking; interstitial brachytherapy; quality assurance

Initial needle tracking with the first standalone combined infrared camera – CT system for brachytherapy—analysis of tracking accuracy and uncertainties - Karius, Andre; Leifeld, Lisa Marie; Strnad, Vratislav; Schweizer, Claudia; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2024)
Purpose: A prototype infrared camera – cone-beam computed tomography (CBCT) system for tracking in brachytherapy has recently been developed. We evaluated for the first time the corresponding tracking accuracy and uncertainties, and implemented a tracking-based prediction of needles on CBCT scans. Methods: A marker tool rigidly attached to needles was 3D printed. The precision and accuracy of tool tracking was then evaluated for both static and dynamic scenarios. Euclidean distances between the tracked and CBCT-derived markers were assessed as well. To implement needle tracking, ground truth models of the tool attached to 200 mm and 160 mm needles were matched to the tracked positions in order to project the needles into CBCT scans. Deviations between projected and actual needle tips were measured. Finally, we put our results into perspective with simulations of the system’s tracking uncertainties. Results: For the stationary scenario and dynamic movements, we achieved tool-tracking precision and accuracy of 0.04 ± 0.06 mm and 0.16 ± 0.18 mm, respectively. The tracked marker positions differed by 0.52 ± 0.18 mm from the positions determined via CBCT. In addition, the predicted needle tips in air deviated from the actual tip positions by only 1.62 ± 0.68 mm (200 mm needle) and 1.49 ± 0.62 mm (160 mm needle). The simulated tracking uncertainties resulted in tip variations of 1.58 ± 0.91 mm and 1.31 ± 0.69 mm for the 200 mm and 160 mm needles, respectively. Conclusion: With the innovative system it was possible to achieve a high tracking and prediction accuracy of marker tool and needles. The system shows high potential for applicator tracking in brachytherapy.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Adaptive treatments; Gynecologic brachytherapy; Needle navigation; Optical tracking; Patient-specific implantations

In Regard to Rahimi et al. - Hannoun-Levi, Jean Michel; Guinot, José Luis; Gutierrez, Cristina; Polgar, Csaba; Strnad, Vratislav (International Journal of Radiation Oncology Biology Physics, 2022)
CRIS-Team Scopus Importer:2022-05-20

In Regard to Shaitelman et al. - Kaidar-Person, Orit; Strnad, Vratislav; Ratosa, Ivica; Boersma, Liesbeth; Poortmans, Philip (Practical Radiation Oncology, 2024)
CRIS-Team Scopus Importer:2024-11-08

In regard to Van den Bruele AB et al. Management of ipsilateral breast tumor recurrence following breast conservation surgery: a comparative study of re-conservation vs mastectomy. Breast Cancer Res Treat. 2021 May;187(1):105-112. doi:10.1007/s10549-020-06080-9. Epub 2021 Jan 12. PMID: 33433775; PMCID: PMC8068641 - Hannoun-Levi, Jean-Michel; Polgar, Csaba; Strnad, Vratislav (Breast Cancer Research and Treatment, 2021)
CRIS-Team WoS Importer:2021-08-20

INTERNATIONAL EXPERT DELPHI CONSENSUS GUIDELINES FOR THE USE OF BOLUS IN POST MASTECTOMY RADIATION THERAPY - Dahn, Hannah; Boersma, Liesbeth; De Ruysscher, Dirk; Meattini, Icro; Offersen, Birgitte; Pignol, Jean-Philippe; Aristei, Cynthia; Benjamin, Dori; Bese, Nuran; Coles, Charlotte; Franco, Pierfrancesco; Ho, Alice; et al. (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-10

Inter-observer effects in needle reconstruction for temporary prostate brachytherapy: Dosimetric implications and adaptive CBCT-TRUS registration solutions - Karius, Andre; Kreppner, Stephan; Strnad, Vratislav; Schweizer, Claudia; Lotter, Michael; Fietkau, Rainer; Bert, Christoph (Brachytherapy, 2024)
PURPOSE: To investigate geometric and dosimetric inter-observer variability in needle reconstruction for temporary prostate brachytherapy. To assess the potential of registrations between transrectal ultrasound (TRUS) and cone-beam computed tomography (CBCT) to support implant reconstructions. METHODS AND MATERIALS: The needles implanted in 28 patients were reconstructed on TRUS by three physicists. Corresponding geometric deviations and associated dosimetric variations to prostate and organs at risk (urethra, bladder, rectum) were analyzed. To account for the found inter-observer variability, various approaches (template-based, probe-based, marker-based) for registrations of CBCT to TRUS were investigated regarding the respective needle transfer accuracy in a phantom study. Three patient cases were examined to assess registration accuracy in-vivo. RESULTS: Geometric inter-observer deviations >1 mm and >3 mm were found for 34.9% and 3.5% of all needles, respectively. Prostate dose coverage (changes up to 7.2%) and urethra dose (partly exceeding given dose constraints) were most affected by associated dosimetric changes. Marker-based and probe-based registrations resulted in the phantom study in high mean needle transfer accuracies of 0.73 mm and 0.12 mm, respectively. In the patient cases, the marker-based approach was the superior technique for CBCT-TRUS fusions. CONCLUSION: Inter-observer variability in needle reconstruction can substantially affect dosimetry for individual patients. Especially marker-based CBCT-TRUS registrations can help to ensure accurate reconstructions for improved treatment planning.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Cone-beam computed tomography; Image registration; Inter-observer variation; Needle reconstruction; Temporary prostate brachytherapy; Transrectal ultrasound

Interstitial High-Dose-Rate Brachytherapy Combined with External Beam Radiation Therapy for Dose Escalation in the Primary Treatment of Locally Advanced, Non-Resectable Superior Sulcus (Pancoast) Tumors: Results of a Monocentric Retrospective Study - Neu, Maria; Kahl, Klaus Henning; Körner, Melina; Walter, Renate; Raab, Stephan; Jehs, Bertram; Käsmann, Lukas; Strnad, Vratislav; Stüben, Georg; Balagiannis, Nikolaos (Journal of Clinical Medicine, 2024)
Objectives: To analyze the results of interstitial (IRT) high-dose-rate (HDR) brachytherapy (BT) in the primary treatment of patients with unresectable superior sulcus tumors (SST) combined with external beam radiotherapy (EBRT). Methods: Between 2013 and 2023, seven patients with unresectable SST were treated with combined BT and EBRT with or without concomitant chemotherapy. The patients’ median age was 64 years (range, 49–79 years) and median tumor volume was 146.8 cm3 (range, 29.3–242.3 cm3). A median BT dose of 8 Gray (Gy) (range, 5–10 Gy) was prescribed and delivered in a single fraction. A median EBRT dose of 54 Gy (range, 30–59 Gy) was prescribed and administered normofractionated (single dose: 1.8 Gy). Results: We report the results of seven patients with SST treated with combined BT and EBRT and followed for a median of 38 months. The overall clinical response rate was 83.33% with five out of six patients achieving local control, while one out of six (16.66%) showed local and general progression. No deaths were attributed to the treatment itself; rather, one patient died during the course of therapy as a result of systemic progression. The most common radiation-related adverse events were grade I–II fatigue and mild paresthesia. No severe toxicity (CTCAE ≥ III°) was observed with interstitial high-dose-rate (HDR) BT combined with EBRT. Conclusions: For patients with unresectable superior sulcus tumors, interstitial HDR BT in combination with EBRT is a feasible treatment option that offers the potential for local control and long-term survival. The findings of this study should be validated in a larger patient cohort.
CRIS-Team Scopus Importer:2025-02-04
Keywords: combined with EBRT; dose escalation; high-dose-rate; interstitial brachytherapy; locally advanced superior sulcus tumor; unresectable pancoast tumor

Investigating the impact of breast positioning control on physical treatment parameters in multi-catheter breast brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2023)
Purpose: To assess the effects of a workflow for reproducible patient and breast positioning on implant stability during high-dose-rate multi-catheter breast brachytherapy. Methods: Thirty patients were treated with our new positioning control workflow. Implant stability was evaluated based on a comparison of planning-CTs to control-CTs acquired halfway through the treatment. To assess geometric stability, button–button distance variations as well as Euclidean dwell position deviations were evaluated. The latter were also quantified within various separated regions within the breast to investigate the location-dependency of implant alterations. Furthermore, dosimetric variations to target volume and organs at risk (ribs, skin) as well as isodose volume changes were analyzed. Results were compared to a previously treated cohort of 100 patients. Results: With the introduced workflow, the patient fraction affected by button–button distance variations > 5 mm and by dwell position deviations > 7 mm were reduced from 37% to 10% and from 30% to 6.6%, respectively. Implant stability improved the most in the lateral to medial breast regions. Only small stability enhancements were observed regarding target volume dosimetry, but the stability of organ at risk exposure became substantially higher. D0.2ccm skin dose variations > 12.4% and D0.1ccm rib dose variations > 6.7% were reduced from 11% to 0% and from 16% to 3.3% of all patients, respectively. Conclusion: Breast positioning control improved geometric and dosimetric implant stability for individual patients, and thus enhanced physical plan validity in these cases.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Adaptive brachytherapy; Computed tomography; Implant stability; Treatment quality; Treatment re-planning

Irradiation of the locoregional Lymphatic Drainage Pathways of Breast Cancer: Is the prescribed Dose actually applied? A Planning Study by the DEGRO Breast Cancer Working Group - Duma, M. N.; Piroth, M.; Fastner, G.; Baumann, R.; Combs, S.; Dunst, J.; Feyer, P.; Fietkau, Rainer; Haase, W.; Harms, W.; Hehr, T.; Krug, D.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Is model-based dose calculation based on cone-beam computed tomography suitable for adaptive treatment planning in brachytherapy? - Karius, Andre; Shariff, Maya; Schaller, Sabrina; Lotter, Michael; Strnad, Vratislav; Lackner, Niklas; Fietkau, Rainer; Bert, Christoph; Merten, Ricarda; Schweizer, Claudia (Strahlentherapie und Onkologie, 2024)
Background and purpose: Model-based dose calculation considering tissue compositions is increasingly being investigated in brachytherapy. The aim of this study was to assess the suitability of modern cone-beam computed tomography (CBCT) imaging compared to conventional computed tomography (CT) scans for this purpose. Materials and methods: By means of a phantom study, we evaluated the CT numbers and electron densities measured using a modern CBCT device as well as a conventional CT scanner for various materials. Based on this, we compared dose calculations (using the TG-43 formalism as well as model-based collapsed cone calculations assuming uniform materials [ACEuniform] and considering CT numbers [ACECT#]) on planning CTs and control CBCTs for patients with cervical and breast cancer as well as phantom-simulated skin cancer cases. Assessing dosimetric deviations between the planning CTs and control CBCTs acquired during the treatment course served to estimate interfractional implant variations. Results: The comparison of ACEuniform–ACECT# deviations between planning CTs and control CBCTs revealed no statistically significant difference for almost all examined dose parameters. Dosimetric deviations between model-based dose calculations and TG-43 were partly significant but of small magnitude (< 10 cGy per fraction). Interfractional dosimetric variations were substantially larger than the dosimetric differences found between the various dose calculation procedures. Conclusion: Model-based dose calculation based on modern CBCT imaging was suitable. However, the found differences between these calculations and the TG-43 formalism should be investigated in dose–outcome analyses. The observed interfractional dosimetric variations revealed the importance of performing treatment quality assurance.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Adaptive radiotherapy; Brachytherapy; Breast cancer; Cervical cancer; Model-based dose calculation

Letter comments on: The impact of isolated local recurrence on long-term outcome in early-breast cancer patients after breast-conserving therapy - Hannoun-Levi, Jean Michel; Gutierrez, Cristina; Polgar, Csaba; Strnad, Vratislav (European Journal of Cancer, 2021)
CRIS-Team Scopus Importer:2021-11-19

Letter to the Editor: Reply to Topkan et al - Schweizer, Claudia; Strnad, Vratislav (Clinical and Translational Radiation Oncology, 2025)
We thank the colleagues Topkan and the co-authors for their valuable comments on our study. As they stated correctly, there for sure are more factors influencing the development of necrosis – nicotine and alcohol might also play an important role, for example. Also some hints point at the distance of the catheters being associated with risk of necrosis. Due to the fact that the risk factors influence each other in their effect on the risk of necrosis and usually have an additive effect and due to the generally retrospective data collections in published articles on interventional radiotherapy in the oral cavity, some risk factors for late side effects cannot be perfectly recorded and evaluated. In our understanding, not only the distance to the mandible, but also the bone volume which is affected by radiation dose must be considered. No specific dose constraints exist for the mandible when applying interventional radiotherapy. We are currently analyzing further dose parameters available within CT-based planning workflows and hope for more detailed information on how we can improve the implants. Nevertheless, prospective data is needed to sufficiently address toxicity issues in a larger cohort of patients with long-term follow-up. As far as the disease-free survival is concerned, we indeed estimated this according to the current practice in several other published data without taking the event of death into account. This is obvious when looking at our results. Still, we agree that the different ways of presenting freedom of recurrence throughout the literature makes comparison rather difficult and should be unified. We thank you for your remark and will consider this in our future work.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Early-stage oral cavity cancer; Interventional radiotherapy; Long-term toxicity after brachytherapy; Postoperative radiotherapy

Localization of reference points in electromagnetic tracking data and their application for treatment error detection in interstitial breast brachytherapy - Dürrbeck, Christopher; Schuster, Sabrina; Sauer, Birte; Abu-Hossin, Nadin; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: Electromagnetic tracking (EMT) is a promising technology that holds great potential to advance patient-specific pre-treatment verification in interstitial brachytherapy (iBT). It allows easy determination of the implant geometry without line-of-sight restrictions and without dose exposure to the patient. What it cannot provide, however, is a link to anatomical landmarks, such as the exit points of catheters or needles on the skin surface. These landmarks are required for the registration of EMT data with other imaging modalities and for the detection of treatment errors such as incorrect indexer lengths, and catheter or needle shifts. Purpose: To develop an easily applicable method to detect reference points in the positional data of the trajectory of an EMT sensor, specifically the exit points of catheters in breast iBT, and to apply the approach to pre-treatment error detection. Methods: Small metal objects were attached to catheter fixation buttons that rest against the breast surface to intentionally induce a local, spatially limited perturbation of the magnetic field on which the working principle of EMT relies. This perturbation can be sensed by the EMT sensor as it passes by, allowing it to localize the metal object and thus the catheter exit point. For the proof-of-concept, different small metal objects (magnets, washers, and bushes) and EMT sensor drive speeds were used to find the optimal parameters. The approach was then applied to treatment error detection and validated in-vitro on a phantom. Lastly, the in-vivo feasibility of the approach was tested on a patient cohort of four patients to assess the impact on the clinical workflow. Results: All investigated metal objects were able to measurably perturb the magnetic field, which resulted in missing sensor readings, that is two data gaps, one for the sensor moving towards the tip end and one when retracting from there. The size of the resulting data gaps varied depending on the choice of gap points used for calculation of the gap size; it was found that the start points of the gaps in both directions showed the smallest variability. The median size of data gaps was ⩽8 mm for all tested materials and sensor drive speeds. The variability of the determined object position was ⩽0.5 mm at a speed of 1.0 cm/s and ⩽0.7 mm at 2.5 cm/s, with an increase up to 2.3 mm at 5.0 cm/s. The in-vitro validation of the error detection yielded a 100% detection rate for catheter shifts of ≥2.2 mm. All simulated wrong indexer lengths were correctly identified. The in-vivo feasibility assessment showed that the metal objects did not interfere with the routine clinical workflow. Conclusions: The developed approach was able to successfully detect reference points in EMT data, which can be used for registration to other imaging modalities, but also for treatment error detection. It can thus advance the automation of patient-specific, pre-treatment quality assurance in iBT.
CRIS-Team Scopus Importer:2023-07-28
Keywords: brachytherapy; electromagnetic tracking; error detection; quality assurance

Low-dose-rate Prostate Brachytherapy: Characterization of Seeds Dynamics within the Prostate - Karius, Andre; Lotter, M.; Kreppner, Stephan; Lubgan, Dorota; Grigo, Johanna; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Oligometastasis in breast cancer—current status and treatment options from a radiation oncology perspective - Piroth, Marc D.; Krug, David; Feyer, Petra; Baumann, Rene; Combs, Stephanie; Duma, Marciana-Nona; Dunst, Juergen; Fastner, Gerd; Fietkau, Rainer; Guckenberger, Matthias; Haase, Wulf; Harms, Wolfgang; et al. (Strahlentherapie und Onkologie, 2022)
Evidence from a few small randomized trials and retrospective cohorts mostly including various tumor entities indicates a prolongation of disease free survival (DFS) and overall survival (OS) from local ablative therapies in oligometastatic disease (OMD). However, it is still unclear which patients benefit most from this approach. We give an overview of the several aspects of stereotactic body radiotherapy (SBRT) in extracranial OMD in breast cancer from a radiation oncology perspective. A PubMed search referring to this was conducted. An attempt was made to relate the therapeutic efficacy of SBRT to various prognostic factors. Data from approximately 500 breast cancer patients treated with SBRT for OMD in mostly in small cohort studies have been published, consistently indicating high local tumor control rates and favorable progression-free (PFS) and overall survival (OS). Predictors for a good prognosis after SBRT are favorable biological subtype (hormone receptor positive, HER2 negative), solitary metastasis, bone-only metastasis, and long metastasis-free interval. However, definitive proof that SBRT in OMD breast cancer prolongs DFS or OS is lacking, since, with the exception of one small randomized trial (n = 22 in the SBRT arm), none of the cohort studies had an adequate control group. Further studies are needed to prove the benefit of SBRT in OMD breast cancer and to define adequate selection criteria. Currently, the use of local ablative SBRT should always be discussed in a multidisciplinary tumor board.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Breast cancer; Oligometastases; OMD; Radiotherapy; Stereotactic body radiotherapy

On the implant stability in adaptive multi-catheter breast brachytherapy: Establishment of a decision-tree for treatment re-planning - Karius, Andre; Szkitsak, Juliane; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Schubert, Philipp; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2023)
Background and purpose: To assess implant stability and identify causes of implant variations during high-dose-rate multi-catheter breast brachytherapy. Materials and methods: Planning-CTs were compared to control-CTs acquired halfway through the treatment for 100 patients. For assessing geometric stability, Fréchet-distance and button-to-button distance changes of all catheters as well as variations of Euclidean distances and convex hulls of all dwell positions were determined. The CTs were inspected to identify the causes of geometric changes. Dosimetric effects were evaluated by target volume transfers and re-contouring of organs at risk. The dose non-uniformity ratio (DNR), 100% and 150% isodose volumes (V100 and V150), coverage index (CI), and organ doses were calculated. Correlations between the examined geometric and dosimetric parameters were assessed. Results: Fréchet-distance and dwell position deviations >2.5 mm as well as button-to-button distance changes >5 mm were detected for 5%, 2%, and 6.3% of catheters, but for 32, 17, and 37 patients, respectively. Variations occurred enhanced in the lateral breast and close to the ribs, e.g. due to different arm positions. Only small dosimetric effects with median DNR, V100, and CI variations of −0.01 ± 0.02, (−0.5 ± 1.3)ccm, and (–1.4 ± 1.8)% were observed in general. Skin dose exceeded recommended levels for 12 of 100 patients. Various correlations between geometric and dosimetric implant stability were found, based on which decision-tree regarding treatment re-planning was established. Conclusion: Multi-catheter breast brachytherapy shows a high implant stability in general, but considering skin dose changes is important. To increase implant stability for individual patients, we plan to investigate patient immobilization aids during treatments.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Adaptive brachytherapy; CT imaging; Imaging-based treatment planning; Implant stability; Multi-catheter breast brachytherapy; Treatment quality assurance

Outcomes of I-125 Low-Dose-Rate Brachytherapy in Patients with Localized Prostate Cancer: A Comprehensive Analysis from a Specialized Tertiary Referral Center - Schubert, Philipp; Strnad, Vratislav; Höfler, Daniel; Schweizer, Claudia; Putz, Florian; Lotter, Michael; Kreppner, Stephan; Karius, Andre; Fietkau, Rainer; Merten, Ricarda (Journal of Personalized Medicine, 2024)
Low-dose-rate (LDR) brachytherapy with I-125 seeds is one of the most common primary tumor treatments for low-risk and low-intermediate-risk prostate cancer. This report aimed to present an analysis of single-institution long-term results. We analyzed the treatment outcomes of 119 patients with low- and intermediate-risk prostate cancer treated with LDR brachytherapy at our institution between 2014 and 2020. The analysis focused on biochemical recurrence rates (BRFS), overall survival (OS), cumulative local recurrence rate (CLRR), and the incidence of acute and late toxicities. Patient-reported quality of life measures were also evaluated to provide a holistic view on the treatment’s impact. The median follow-up period was 46 months. CLRR was 3.3% (4/119), five-year BRFS was 87%, and the five-year OS rate was 95%. Dysuria was the most common acute urinary toxicity, reported in 26.0% of patients as grade 1 and 13.4% as grade 2. As a late side effect, 12.6% of patients experienced mild dysuria. Sexual dysfunction persisted in 6.7% of patients as grade 1, 7.5% as grade 2, and 10.0% as grade 3. LDR brachytherapy in patients with prostate cancer is an effective treatment, with favorable clinical outcomes and manageable toxicity. The low CLRR and high OS rates, as well as low incidence of severe side effects, support the continued use of LDR brachytherapy as a primary treatment modality for localized prostate cancer.
CRIS-Team Scopus Importer:2024-09-06
Keywords: I-125 seeds; LDR brachytherapy; low-intermediate-risk prostate cancer; low-risk prostate cancer; patient-reported outcomes; prostate cancer; toxicity; treatment outcomes

Permanent LDR prostate brachytherapy: Comprehensive characterization of seed-dynamics within the prostate on a seed-only level - Karius, Andre; Lotter, Michael; Kreppner, Stephan; Schaller, Verena; Lubgan, Dorota; Grigo, Johanna; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Brachytherapy, 2022)
PURPOSE: Seed brachytherapy is a well-established treatment modality for prostate cancer. However, there is still a lack of profound characterizations of seed motions within the prostate. We assessed these dynamics between day 0 and day 30 of brachytherapy. METHODS: We considered 45 patients with 2408 implanted seeds, and performed a 1:1 assignment between their positions on post-plan CT (nominal day 30) and intraoperative ultrasound (day 0). Geometric seed arrangement changes were measured for each patient and the entire collective. The impact of seed strand-lengths and implant regions was investigated. Correlations with patient characteristics were evaluated. We determined corresponding dosimetric effects by calculating common dose metrics. RESULTS: We found a median seed displacement of 4.3 mm [interquartile range: 3.1–6.9 mm], occurring preferentially in superior-inferior direction. Single and double strands moved significantly stronger than strands of higher lengths. Seed dynamics was more pronounced in base (5.6 mm [3.7–10.7 mm]) and apex (6.5 mm [4.1–15.0 mm]) than in the mid-gland (3.8 mm [2.7–5.0 mm]), and less pronounced in peripheral (4.3 mm [3.0–6.7 mm]) than in urethra-near (5.5 mm [3.5–10.7 mm]) regions. Correlations of seed dynamics with prostate volume changes and the number of implanted seeds and needles were found. D90 (dose that 90% of the prostate receives) varied by a median of 3 Gy [-6 to 15 Gy] between treatment plan and post-plan, but >40 Gy for individual patients. CONCLUSIONS: Reducing seed dynamics is important to ensure a high treatment quality. For this, strands containing ≥3 seeds may be useful, implantations in base-, apex-, and urethra-near zone should be avoided, and the number of needles and seeds may be minimized where possible.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Adaptive Brachytherapy; Low-dose-rate prostate brachytherapy; Prostate Cancer; Seed brachytherapy; Seed displacements

Phase II Study: Accelerated Partial Breast Irradiation (APBI) on a Linear Accelerator - Ott, Oliver; Schweizer, Claudia; Strnad, Vratislav; Stillkrieg, W.; Lambrecht, U.; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Possibilities of a Seed Control after the Implantation by using MRI and Deep Learning-based QSM Reconstruction - Grigo, Johanna; Karius, Andre; Hanspach, Jannis; Weissmann, Thomas; Laun, Frederik Bernd; Strnad, Vratislav; Putz, Florian; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Postoperative brachytherapy alone for 217 patients with early-stage oral cavity squamous cell carcinoma - Schweizer, Claudia; Strnad, Vratislav; Lotter, M.; Kreppner, Stephan; Merten, Ricarda; Fietkau, Rainer; Karius, Andre (Clinical and Translational Radiation Oncology, 2025)
Introduction: Postoperative radiotherapy is generally recommended for pT1/2pN0 squamous cell carcinoma of the oral cavity (OSCC) if risk factors are present. Prospective studies are missing. Interventional radiotherapy offers a precise dose application. In this paper we analyze long-term efficacy and toxicity in a large single-center cohort of patients with early OSCC receiving sole postoperative brachytherapy (BT). Material and methods: From 1998 to 2023, 217 patients were postoperatively treated with sole BT in our institute. The median follow-up was 110 months (range: 2–316). The primary objective was local control. Secondary outcomes were overall survival, cancer specific survival, and toxicity. Results: The local recurrence rates for 12, 24, and 60 months were 7.1 %, 9.1 %, and 12.6 %. The disease-free survival was 89.7 %, 86.1 %, and 79.3 %. The overall survival rates at 12, 24, and 60 months were 94.4 %, 89.6 %, and 77.9 %. The cancer-specific survival was 97.1 %, 96.6 %, and 92.9 %, respectively. At two years, the rate of regional recurrence was 8.3 %. Patients without neck dissection had a significantly increased risk for lymph node recurrence (p = 0.025). Side effects ≥ grade 3 were seen in 14 % (30/217). 17 % (37/217) of patients developed a soft tissue necrosis (STN). Osteoradionecrosis (ORN) was seen in 7 % (15/217) of patients. A target volume > 15 cm3 was significantly associated with the occurrence of STN (p = 0.011) and ORN (p = 0.004). Conclusions: Postoperative interventional radiotherapy for previously not irradiated patients with early-stage OSCC is a safe and efficient treatment. Randomized trials are needed to compare these results to omission of postoperative radiotherapy as well as external beam radiotherapy.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Early-stage oral cavity cancer; HDR; Interventional radiotherapy; Long-term toxicity after brachytherapy; PDR; Postoperative radiotherapy

Post- versus intra-operative implant for breast cancer interstitial brachytherapy: How to choose? - Gimeno-Morales, Marta; Motisi, Laura; Rodriguez-Spiteri, Natalia; Martínez-Regueira, Fernando; Therapist, Tucker Worthington Radiation; Strnad, Vratislav; Hannoun-Levi, Jean Michel; Gutierrez, Cristina (Journal of Contemporary Brachytherapy, 2024)
Purpose: Breast brachytherapy (BB) represents an important radiation therapy modality in modern breast cancer treatments. Currently, BB is mainly used for accelerated partial breast irradiation (APBI), local boost after whole breast radiation therapy (WBRT), and as salvage re-irradiation after second lumpectomy (APBrl). Two multi-catheter interstitial brachytherapy (MIB) techniques can be offered: intra-operative (IOB) and post-operative (POB) brachytherapy. The aim of this article was to summarize current available data on these two different brachytherapy approaches for breast cancer. Material and methods: A literature search was performed, and different experiences published by BB expert teams were analyzed and compared. These two different brachytherapy approaches for breast cancer have also been presented and discussed during meetings of the GEC-ESTRO BCWG. In addition, expert recommendations were defined. Results: A comprehensive description and practical comparison of both the techniques, i.e., IOB and POB, considering the latest available published data were presented. Different technical, logistic, and clinical aspects of both the methods were thoroughly examined and analyzed. This detailed comparison of the two breast brachytherapy techniques was supported by scientific data from extensive experience of experts, facilitating an objective analysis that, to our knowledge, has not been previously published. Conclusions: Based on the comprehensive analysis of both the brachytherapy techniques available, this article serves as a valuable resource to guide breast teams in selecting the optimal BB technique (POB or IOB), considering hospital environment, multi-disciplinary collaboration, and patient logistics.
CRIS-Team Scopus Importer:2024-05-03
Keywords: accelerated partial breast irradiation; brachytherapy; breast cancer; intra-operative brachytherapy; post-operative brachytherapy

Prostate brachytherapy boost: Long-term results of protocol-based treatment of patients with non-metastatic prostate cancer. - Schweizer, Claudia; Strnad, Vratislav; Merten, Ricarda; Schubert, Philipp; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Karius, Andre (Journal of Contemporary Brachytherapy, 2024)
PURPOSE: To evaluate the efficacy and toxicity of interstitial temporary brachytherapy boost for prostate cancer patients using real-world data. MATERIAL AND METHODS: Between 2008 and 2016, 115 patients treated with external beam radiotherapy (EBRT) followed by a brachytherapy boost (BT boost) were eligible for this retrospective analysis. Patients received either interstitial high-dose-rate brachytherapy (HDR-BT) with 2 x 9-9.5 Gray (Gy) schedule or pulsed-dose-rate brachytherapy (PDR-BT) with 35 Gy as boost after EBRT (50.4 Gy), up to a total dose of 86-98 Gy (EQD2α/β = 3). Primary endpoints of the present analysis were cumulative local recurrence rate (LRR), biochemical recurrence-free survival (bRFS), tumor-specific survival, and overall survival (OS). As secondary objective, treatment-related toxicity was evaluated. RESULTS: The median follow-up time was 87 (range, 9-159) months, and the median age was 72 (range, 48-83) years. The median prostate specific antigen value (PSA) was 12.2 (range, 2.4-288) ng/ml. 78/115 (68%) patients had high-risk prostate cancer according to the D'Amico classification. At 7 years, the cumulative LRR for the whole cohort was 1.8%. The 7-year bRFS, cancer-specific survival, and OS were 85.2%, 97.3%, and 88.9%. The 5-year prevalence of late toxicity grade 3 or higher according to the LENT-SOMA scale was 4%. There were no significant differences for treatment outcome or toxicity for HDR vs. PDR treatment. A prostate gland of 50 cm3 or more was not associated with worse treatment efficacy or increased side effects, apart from the prevalence of urethritis after 5 years (p = 0.035). CONCLUSIONS: BT boost in patients with prostate cancer is efficient and well-tolerated, with low rates of side effects also in elderly patients. HDR- and PDR-BT were equally efficient and well-tolerated. A large prostate gland is no contraindication for BT. Therefore, BT boost should be offered to all eligible patients.
EVALuna2:595654

Risk-adapted modulation through deintensification of cancer treatments: an ESMO classification - Hannoun-Levi, J. M.; Gutierrez, C.; Polgar, C.; Strnad, Vratislav (Annals of Oncology, 2022)
CRIS-Team Scopus Importer:2022-10-21

Role of Brachytherapy in the Postoperative Management of Endometrial Cancer: Decision-Making Analysis among Experienced European Radiation Oncologists - Glatzer, Markus; Tanderup, Kari; Rovirosa, Angeles; Fokdal, Lars; Ordeanu, Claudia; Tagliaferri, Luca; Chargari, Cyrus; Strnad, Vratislav; Dimopoulos, Johannes Athanasios; Šegedin, Barbara; Cooper, Rachel; Nakken, Esten Søndrol; et al. (Cancers, 2022)
Background: There are various society-specific guidelines addressing adjuvant brachytherapy (BT) after surgery for endometrial cancer (EC). However, these recommendations are not uniform. Against this background, clinicians need to make decisions despite gaps between best scientific evidence and clinical practice. We explored factors influencing decision-making for adjuvant BT in clinical routine among experienced European radiation oncologists in the field of gynaecological radiotherapy (RT). We also investigated the dose and technique of BT. Methods: Nineteen European experts for gynaecological BT selected by the Groupe Européen de Curiethérapie and the European Society for Radiotherapy & Oncology provided their decision criteria and technique for postoperative RT in EC. The decision criteria were captured and converted into decision trees, and consensus and dissent were evaluated based on the objective consensus methodology. Results: The decision criteria used by the experts were tumour extension, grading, nodal status, lymphovascular invasion, and cervical stroma/vaginal invasion (yes/no). No expert recommended adjuvant BT for pT1a G1-2 EC without substantial LVSI. Eighty-four percent of experts recommended BT for pT1a G3 EC without substantial LVSI. Up to 74% of experts used adjuvant BT for pT1b LVSI-negative and pT2 G1–2 LVSI-negative disease. For 74–84% of experts, EBRT + BT was the treatment of choice for nodal-positive pT2 disease and for pT3 EC with cervical/vaginal invasion. For all other tumour stages, there was no clear consensus for adjuvant treatment. Four experts already used molecular markers for decision-making. Sixty-five percent of experts recommended fractionation regimens of 3 × 7 Gy or 4 × 5 Gy for BT as monotherapy and 2 × 5 Gy for combination with EBRT. The most commonly used applicator for BT was a vaginal cylinder; 82% recommended image-guided BT. Conclusion: There was a clear trend towards adjuvant BT for stage IA G3, stage IB, and stage II G1–2 LVSI-negative EC. Likewise, there was a non-uniform pattern for BT dose prescription but a clear trend towards 3D image-based BT. Finally, molecular characteristics were already used in daily decision-making by some experts under the pretext that upcoming trials will bring more clarity to this topic.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Brachytherapy; Decision tree; Decision-making; Endometrial cancer

Safety and Efficacy of Brachytherapy in Inoperable Endometrial Cancer - Merten, Ricarda; Strnad, Vratislav; Schweizer, Claudia; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Schubert, Philipp; Karius, Andre; Schubert, Philipp (Journal of Personalized Medicine, 2024)
Background/Objectives: Radiotherapy represents the only treatment option for patients with inoperable endometrial cancer (EC). The aim of our study was to evaluate the efficacy and safety of brachytherapy (BT) in this selected patient population. Methods: Between 1990 and 2019, 18 patients with inoperable EC in stage FIGO I–IV were treated with intracavitary brachytherapy using the “Heyman Packing technique”. BT was performed either as sole PDR- or HDR-brachytherapy with a median cumulative dose up to 60.0 Gy (67.9 Gy EQD2 α/β = 3Gy) and 34.0 Gy (75.6 Gy EQD2 α/β = 3Gy), respectively. Results: The median follow-up was 46 months (6–219). The mean age was 71 years. The 5-year cumulative local recurrence rate (CLRR) for the whole cohort was 27.3%. The 5-year overall survival (OS), distant metastasis-free survival (DMFS), and disease-free survival (DFS) were 51%, 79%, and 69%. The 5-year DFS for low-, intermediate-, and high-risk EC was 89%, 50%, and 44% (p = 0.51). No significant difference in DFS was observed in patients over 70 (p = 0.526). No late side effects of grade > 1 were documented. Conclusions: Brachytherapy for inoperable EC is a safe and effective treatment option, offering good local control and OS with minimal toxicity. Moreover, brachytherapy effectively controls hemoglobin-relevant bleeding. Therefore, BT should be considered a viable alternative to non-curative treatment strategies in gynecological multidisciplinary conferences.
CRIS-Team Scopus Importer:2025-02-04
Keywords: brachytherapy; definitive treatment; endometrial cancer; hemostyptic irradiation; inoperable

Salvage brachytherapy for local recurrence of cancer after definitive irradiation: a GEC-ESTRO narrative review - Hannoun-Levi, J. M.; Strnad, Vratislav; Eminowicz, G.; de Iturriaga, A. Gomez; Smanykó, V.; Tagliaferri, L.; Stewart, A.; Siebert, F. A. (Radiotherapy and Oncology, 2025)
The number of irradiated cancer survivors is increasing; mainly for breast, prostate, head-and-neck, uterine and rectal cancers. Due to multiple factors including life expectancy, increasing cancer incidence and intensive cancer treatment improvements, cancer re-irradiation is an increasing phenomenon. Local recurrence of cancer after after definitive irradiation represents one of the most challenging therapeutic scenarios. The goal is to deliver to a pre-irradiated volume, a high dose (achieving secondary local control) while sparing organs at risk from deleterious over-dose (side effects). Among the different re-irradiation techniques, salvage brachytherapy (BT), due to its “Trojan horse” concept, delivers the dose directly inside the target volume with a sharp dose fall-off and low integral dose compared to external beam radiotherapy techniques. GEC-ESTRO aims to report a narrative review of the literature for salvage BT-based cancer re-irradiation for the most frequent cancers (PubMed search key words: local recurrence treatment, re-irradiation, brachytherapy, breast, prostate, head and neck, uterine and rectal cancers). GEC-ESTRO working group representatives reported for each anatomical site; recommendations for patient selection, oncological outcomes and toxicity for salvage BT. Due to its unique physical properties in terms of dose distributions, BT represents a valuable treatment option for cancer local recurrence. For all indications of salvage BT, patient selection is crucial. Shared decision making with the patient about efficacy / benefit and all potential risks represents a key point of the therapeutic decision-making process.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Breast cancer; Gynaecologic cancer; Head and neck cancer; Local recurrence; Prostate cancer; Rectal cancer; Salvage brachytherapy

Second Conservative Treatment for Local Recurrence Breast Cancer: A GEC-ESTRO Oncological Outcome and Prognostic Factor Analysis - Hannoun-Levi, Jean Michel; Gal, Jocelyn; Polgar, Csaba; Strnad, Vratislav; Loessl, Kristina; Polat, Bulent; Kauer-Domer, Daniela; Schiappa, Renaud; Gutierrez, Crisitna (International Journal of Radiation Oncology Biology Physics, 2023)
Purpose: For second ipsilateral breast tumor event (2nd IBTE), second conservative treatment (2nd CT) combining lumpectomy plus accelerated partial breast reirradiation (APBrI) represents a curative option. The aim of this study was to analyze oncological prognostic factors for patients with a 2nd IBTE treated with 2nd CT. Methods and Materials: An analysis of clinical practices was conducted across 7 academic hospitals/cancer centers in 6 European countries based on the GEC-ESTRO database. Patients presenting a 2nd IBTE occurring after conservative surgery (lumpectomy + axillary evaluation) and irradiation performed for the primary tumor underwent a 2nd CT with brachytherapy-based APBrI. The main outcome was 5-year cumulative incidence (CI) rate of second local relapse. All analyzed patients were classified according to risk groups for Groupe Européen de Curiethérapie–European Society for Therapeutic Radiology and Oncology (GEC-ESTRO) accelerated partial breast irradiation (APBI) and molecular classification and time interval between first and second breast surgery (TIS1S2). Finally, we combined GEC-ESTRO APBI, molecular, and TIS1S2 risk groups, leading to the definition of a new score (named TAM: score based on the combination of time interval [T] between first and second surgery and APBI [A] and molecular [M] classifications) specifically designed for 2nd IBTE oncological outcome analysis. Results: From July 1994 to January 2021, a total of 508 patients received a 2nd CT. At the time of 2nd IBTE, median age was 64.6 years (range, 56.2-72.6). With a median follow-up of 60.9 months (56.2-72.6), the 5-year second local relapse CI rate was 4% (95% confidence interval [95% CI], 2%-6%). The 5-year distant metastasis disease CI rate was 7% (95% CI, 4%-10%). Five-year disease-free and overall survival rates were 89% (95% CI, 86%-93%) and 91% (95% CI, 88%-94%), respectively. In multivariate analysis, TAM score was an independent prognostic factor for all the oncological items (P <.001) except disease-specific survival (P =.07) and overall survival (P =.09). The grade ≥3 late toxicity rate was 12.1%. Conclusions: This analysis of 2nd CT combining lumpectomy with APBrI for 2nd IBTE confirmed the excellent oncological results obtained after 2nd CT. Furthermore, the GEC-ESTRO TAM score appears to be an important prognostic factor, assisting patients and physicians in the decision-making process.
CRIS-Team Scopus Importer:2023-08-11

Seed-displacements in the immediate post-implant phase in permanent prostate brachytherapy - Karius, Andre; Schweizer, Claudia; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Lamrani, Allison; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2023)
Purpose: To investigate differences in seed-displacements between the immediate post-implant phase (day 0–1) and the time to post-plan computed tomography (CT) (day 1–30) in seed prostate brachytherapy. Materials and methods: Seed positions were identified on the intra-operatively created ultrasound-based treatment plan (day 0) and CT scans of day 1 and 30 for 33 patients. The day 1 (30) seed arrangement was registered onto the day 0 (1) arrangement using a seed-only approach. Based on a 1:1 assignment of seeds via the Kuhn-Munkres algorithm, seed-displacements were analyzed. Displacements were evaluated depending on strand-length and anatomical implant location. Resulting dosimetric effects were calculated. Results: Seed-displacements in the immediate post-implant phase (median displacements: 3.8 ± 3.6 mm) were stronger than in the time to post-plan CT (2.1 ± 2.6 mm) and enhanced along the superior-inferior direction. From day 0 to 1, strands containing one (7.3 ± 5.4 mm) or two (8.1 ± 5.8 mm) seeds showed larger displacements than strands of higher lengths (up to 4.2 ± 7.0 mm), whereas no length-dependency was found to day 30. Seeds implanted in base and apex tended to move towards the prostate midzone during both time periods. D90 (dose that 90% of prostate receives) was with variations of 2 ± 15 Gy more stable from day 1 to 30 than in the immediate post-implant phase (−18 ± 11 Gy). Conclusion: Seed-displacements in the immediate post-implant phase was enhanced compared to day 1–30. This may result from uncertainties in the gold-standard ultrasound-based treatment planning and implantation. Adaptive implantation workflows appear useful for ensuring high implant stability from the beginning.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Adaptive implantation; Permanent implant; Prostate brachytherapy; Prostate cancer; Seed brachytherapy; Seed displacements

Single-modality endocrine therapy versus radiotherapy after breast-conserving surgery in women aged 70 years and older with luminal A-like early breast cancer (EUROPA): a preplanned interim analysis of a phase 3, non-inferiority, randomised trial - Meattini, Icro; De Santis, Maria Carmen; Visani, Luca; Scorsetti, Marta; Fozza, Alessandra; Meduri, Bruno; De Rose, Fiorenza; Bonzano, Elisabetta; Prisco, Agnese; Masiello, Valeria; La Rocca, Eliana; Spoto, Ruggero; et al. (Lancet Oncology, 2025)
Background: Optimal therapy following breast-conserving surgery in older adults with low-risk, early-stage breast cancer remains uncertain. The EUROPA trial aims to compare the effects of radiotherapy and endocrine therapy as single-modality treatments on health-related quality of life (HRQOL) and ipsilateral breast tumour recurrence (IBTR) outcomes in this population. Methods: This non-inferiority, phase 3, randomised study was conducted at 18 academic hospitals across Italy (17 centres) and Slovenia (one centre). Eligible patients were women aged 70 years or older with histologically confirmed, stage I, luminal A-like breast cancer, who had undergone breast-conserving surgery and had an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients were randomly assigned (1:1) to receive single-modality endocrine therapy or radiotherapy. Endocrine therapy consisted of daily oral aromatase inhibitors or tamoxifen, for a total planned duration of 5–10 years as per clinical discretion, while radiotherapy was administered as either whole breast or partial breast irradiation, delivered in 5–15 fractions. Randomisation was stratified by health status according to the Geriatric 8 (G8) screening tool and by age, with allocation concealed and no blinding. The co-primary endpoints were the change in HRQOL, assessed by the global health status (GHS) scale of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire 30-item core module at 24 months, and 5-year IBTR rates (not reported here). This preplanned interim analysis was performed once at least 152 patients completed the 24-month GHS HRQOL assessment. The safety population comprised patients who received the study intervention at least once after randomisation. The study is registered with ClinicalTrials.gov, NCT04134598, and is ongoing and actively recruiting. Findings: Between March 4, 2021, and June 14, 2024, 731 women were randomly assigned to receive radiotherapy (n=365) or endocrine therapy (n=366). This analysis included 104 patients in the radiotherapy group and 103 in the endocrine therapy group, with a median follow-up of 23·9 months (IQR 22·9–24·2). Patients were predominantly White (204 [99%] of 207) and the median age was 75·0 years (IQR 73·0–80·0) in the radiotherapy group and 74·0 years (72·0–80·0) in the endocrine therapy group. 86 patients in the radiotherapy group and 75 in the endocrine therapy group completed the 24-month HRQOL assessment. The mean baseline GHS score was 71·9 (SD 19·1) in the radiotherapy group and 75·5 (19·3) in the endocrine therapy group. At 24 months, the age-adjusted, G8 score-adjusted mean change from baseline in GHS was –3·40 (95% CI –7·82 to 1·03; p=0·13) in the radiotherapy group and –9·79 (–14·45 to –5·13; p<0·0001) in the endocrine therapy group, with an adjusted mean difference of 6·39 (0·14 to 12·65; p=0·045) favouring radiotherapy. Treatment-related adverse events were less frequent in the radiotherapy group (65 [67%] of 97 patients) compared with the endocrine therapy group (76 [85%] of 89). The most common grade 3–4 adverse events were arthralgia (six [7%] of 89 in the endocrine therapy group vs 0 of 97 in the radiotherapy group), pelvic organ prolapse (three [3%] vs 0), fatigue, hot flashes, myalgia, bone pain, and fractures (two [2%] vs 0 for each). Serious adverse events were reported in 15 (15%) patients in the radiotherapy group and 13 (15%) in the endocrine therapy group. There were no treatment-related deaths in either group. Interpretation: Endocrine therapy was associated with a greater reduction in HRQOL, as measured by GHS, compared with radiotherapy at 24 months. While these interim results suggest radiotherapy might better preserve HRQOL in older women with low-risk early breast cancer, further data on disease control outcomes and final patient accrual are needed to draw definitive conclusions. Funding: Fondazione Radioterapia Oncologica.
CRIS-Team Scopus Importer:2025-01-31

Strahlentherapie des Zervixkarzinoms: Aktuelle Entwicklungen und Therapiestandards der perkutanen Strahlentherapie und Brachytherapie - Schweizer, Claudia; Strnad, Vratislav (Die Gynäkologie, 2024)
Background: Radiotherapy (RT) is an established component of curative treatment for locally advanced cervical cancer. In recent years substantial progress has been made. Objective: Update of percutaneous RT and brachytherapy (BT) techniques as well as concomitant systemic therapy with an overview of currently relevant data. Material and methods: Presentation of the current state of the art in radio-oncological standards and discussion of recent studies concerning RT and concomitant systemic therapy. Results: The PARCER and RTOG 1203 studies confirmed the benefit of intensity-modulated radiotherapy (IMRT) especially with respect to the toxicity. The results of the EMBRACE‑I study showed outstanding efficacy of 3D image-guided BT. For neoadjuvant chemotherapy, detailed data from the INTERLACE study have not yet been published. The simultaneous and adjuvant immunotherapy with durvalumab did not appear to be advantageous in the CALLA study. First results of the KEYNOTE-A-18 study on simultaneous and adjuvant administration of pembrolizumab are promising. Conclusion: Platinum-based chemoradiotherapy (CRT) is and remains the current standard for locally advanced cervical cancer. Modern radiation techniques, such as IMRT and 3D image-guided BT, are also now standard. Neoadjuvant chemotherapy is currently of no importance. Adjuvant chemotherapy with pembrolizumab is a new useful and important option for persistent and recurrent tumors after CRT with BT. Immunotherapy is about to be implemented in primary treatment schedules but is currently not yet approved.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Brachytherapy; Chemoradiotherapy; Hysterectomy; Immunotherapy; Intensity-modulated radiotherapy

Survey on brachytherapy training among radiation oncology residents in the German-speaking regions of Europe - Knoth, Johannes; Konrad, Stefan; Lössl, Kristina; Motisi, Laura; Mäurer, Matthias; Linde, Philipp; Lindel, Katja; Niehoff, Peter; Strnad, Vratislav; Sturdza, Alina; Corradini, Stefanie (Strahlentherapie und Onkologie, 2023)
Purpose: This survey aimed to determine the perception of brachytherapy training among residents in the DACH region, consisting of Austria, Germany and Switzerland. Material & Methods: An online questionnaire containing 22 questions related to trainee demographics (n = 5) and to brachytherapy training (n = 17) was sent in two iterations in 11/2019 and 02/2020. The following topics were evaluated: institutional support, barriers to training, extent of training, site-specific training (prostate, gynaecology, breast, gastrointestinal and skin), preferences for further training and outlook on overall development of brachytherapy. The responses were mostly based on a Likert scale of 1 to 5, thereby reflecting strength of opinion. Descriptive statistics were used to describe frequencies. Results: Among the 108 respondents, approximately 69% of residents considered the ability to perform brachytherapy independently to be important or somewhat important. However, only 31% of respondents reported to have a dedicated brachytherapy training during residency. The major limitation to achieve independence in performing brachytherapy was seen in a low case load in Austria, in the lack of training in Switzerland and in both of them in Germany. Conclusion: The interest in brachytherapy training among residents in German-speaking countries was generally high, but there is a perceived lack of sufficient case volumes and partially also in formal training opportunities. Fellowships at departments with a high case load as part of a formalised curriculum and dedicated hands-on workshops at national or international conferences might help to overcome these issues.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Career choice; Education; Questionnaire; Survey; Teaching

TARGIT-IORT During Lumpectomy for Breast Cancer Reply - Polgar, Csaba; Strnad, Vratislav; Hannoun-Levi, Jean-Michel; Major, Tibor; Takacsi-Nagy, Zoltan; Fodor, Janos (International Journal of Radiation Oncology Biology Physics, 2021)
CRIS-Team WoS Importer:2021-06-25

Technical evaluation of the cone-beam computed tomography imaging performance of a novel, mobile, gantry-based X-ray system for brachytherapy - Karius, Andre; Karolczak, Marek; Strnad, Vratislav; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2021)
Purpose A novel, mobile cone-beam computed tomography (CBCT) system for image-guided adaptive brachytherapy was recently deployed at our hospital as worldwide first site. Prior to the device's clinical operation, a profound characterization of its imaging performance was conducted. This was essential to optimize both the imaging workflow and image quality for achieving the best possible clinical outcomes. We present the results of our investigations. Methods The novel CBCT-system features a ring gantry with 121 cm clearance as well as a 43.2 x 43.2 cm(2) flat-panel detector, and is controlled via a tablet-personal computer (PC). For evaluating its imaging performance, the geometric reproducibility as well as imaging fidelity, computed tomography (CT)-number accuracy, uniformity, contrast-noise-ratio (CNR), noise characteristics, and spatial resolution as fundamental image quality parameters were assessed. As dose metric the weighted cone-beam dose index (CBDIw) was measured. Image quality was evaluated using standard quality assurance (QA) as well as anthropomorphic upper torso and breast phantoms. Both in-house and manufacturer protocols for abdomen, pelvis, and breast imaging were examined. Results Using the in-house protocols, the QA phantom scans showed altogether a high image quality, with high CT-number accuracy (R-2 > 0.97) and uniformity (<12 Hounsfield Unit (HU) cupping), reasonable noise and imaging fidelity, and good CNR at bone-tissue transitions of up to 28:1. Spatial resolution was strongly limited by geometric instabilities of the device. The breast phantom scans fulfilled clinical requirements, whereas the abdomen and pelvis scans showed severe artifacts, particularly at air/bone-tissue transitions. Conclusion With the novel CBCT-system, achieving a high image quality appears possible in principle. However, adaptations of the standard protocols, performance enhancements in image reconstruction referring to artifact reductions, as well as the extinction of geometric instabilities are imperative.
CRIS-Team WoS Importer:2021-12-24

The current status of brachytherapy in Europe − A GEC-ESTRO Brachy-HERO survey - Johansen, J. G.; Jürgenliemk-Schulz, I. M.; Haddad, H.; Hannoun-Levi, J. M.; Hellebust, T. P.; Guix, B.; Loessl, K.; Pieters, B.; Rao, C.; Strnad, Vratislav; Sturdza, A. E.; Tagliaferri, L.; et al. (Clinical and Translational Radiation Oncology, 2025)
A survey regarding utilisation of brachytherapy was distributed to European brachytherapy professionals. Eighty replies from 26 countries were received, two of which were outside Europe. The replies showed that brachytherapy is still widely used. The main indications for brachytherapy are gynaecological and prostate cancer, with >80 % of the responding countries performing brachytherapy for these indications. There is on average one brachytherapy centre per 0.8 million inhabitants, ranging from 0.4 per million to 2.3 per million inhabitants. The organisation of brachytherapy on national levels also varies from country to country, with less than half of the countries having a central brachytherapy registry. All in all, the survey shows that brachytherapy still plays a role on modern radiotherapy, but the field could benefit from a stronger collaboration both nationally and internationally.
CRIS-Team Scopus Importer:2024-11-15

THE USE OF BOLUS IN POSTMASTECTOMY RADIATION THERAPY FOR BREAST CANCER: A SYSTEMATIC REVIEW - Dahn, Hannah; Boersma, Liesbeth; De Ruysscher, Dirk; Meattini, Icro; Offersen, Birgitte; Pignol, Jean-Philippe; Belkacemi, Yazid; Benjamin, Dori; Bese, Nuran; Coles, Charlotte; Franco, Pierfrancesco; Ho, Alice; et al. (Radiotherapy and Oncology, 2021)
Purpose Post mastectomy radiation therapy (PMRT) reduces locoregional recurrence (LRR) and breast cancer mortality for selected patients. Bolus overcomes the skin-sparing effect of external-beam radiotherapy, ensuring adequate dose to superficial regions at risk of local recurrence (LR). This systematic review summarizes the current evidence regarding the impact of bolus on LR and acute toxicity in the setting of PMRT. Results 27 studies were included. The use of bolus led to higher rates of acute grade 3 radiation dermatitis (pooled rates of 9.6% with bolus vs. 1.2% without). Pooled crude LR rates from thirteen studies (n = 3756) were similar with (3.5%) and without (3.6%) bolus. Conclusions Bolus may be indicated in cases with a high risk of LR in the skin, but seems not to be necessary for all patients. Further work is needed to define the role of bolus in PMRT.
CRIS-Team WoS Importer:2021-12-10
Keywords: breast cancer; mastectomy; radiation therapy; post-mastectomy; PMRT; bolus; tissue compensator

Toward a deep learning-based magnetic resonance imaging only workflow for postimplant dosimetry in I-125 seed brachytherapy for prostate cancer - Grigo, Johanna; Karius, Andre; Hanspach, Jannis; Mücke, Lion; Laun, Frederik B.; Huang, Yixing; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Brachytherapy, 2024)
Background and purpose: The current standard imaging-technique for creating postplans in seed prostate brachytherapy is computed tomography (CT), that is associated with additional radiation exposure and poor soft tissue contrast. To establish a magnetic resonance imaging (MRI) only workflow combining improved tissue contrast and high seed detectability, a deep learning-approach for automatic seed segmentation on MRI-scans was developed. Material and methods: Patients treated with I-125 seed brachytherapy received a postplan-CT and a 1.5 T MRI-scan on nominal day 30 after implantation. For MRI-based seed visualization, DIXON-sequences were acquired and deep learning-based quantitative susceptibility maps (QSM) were generated from 3D-gradient-echo-sequences from 20 patients. Seed segmentations created on CT served as ground truth. For automatic seed segmentation on MRI, a 3D nnU-net model was trained using QSM and DIXON, both solely and combined. Results: Of the implanted seeds 94.8 ± 2.4% were detected with deep learning automatic segmentation entrained on both QSM and DIXON data. Models trained on the individual sequence data-sets performed worse with detection rates of 87.5 ± 2.6% or 88.6 ± 7.5% for QSM and DIXON respectively. The seed centers identified on CT versus QSM and DIXON were on average 1.8 ± 1.3 mm apart. Postimplant dosimetry for evaluation of positioning inaccuracies revealed only small variations of up to 0.4 ± 4.26 Gy in D90 (dose 90% of the prostate receives) between the standard CT-approach and our MRI-only workflow. Conclusion: The proposed deep learning-based MRI-only workflow provided a promisingly accurate and robust seed localization and thus has the potential to compete with current state-of-the-art CT-based postimplant dosimetry in the future.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Magnetic resonance imaging; Magnetic resonance only workflow; Permanent brachytherapy; Postimplant dosimetry; Radiotherapy; Seed brachytherapy

Tricks and tips for target volume definition and delineation in breast cancer: Lessons learned from ESTRO breast courses - Kaidar-Person, Orit; Offersen, Birgitte V.; Boersma, Liesbeth; Meattini, Icro; Dodwell, David; Wyld, Lynda; Aznar, Marianne; Major, Tibor; Kuehn, Thorsten; Strnad, Vratislav; Palmu, Miika; Hol, Sandra; et al. (Radiotherapy and Oncology, 2021)
Delineation of target and ‘organ at risk’ volumes is a critical part of modern radiation therapy planning, the next essential step after deciding the indication, patient discussion and image acquisition. Adoption of volume-based treatment planning for non-metastatic breast cancer has increased greatly along with the use of improved planning techniques, essential for modern therapy. However, identifying the volumes on a planning CT is no easy task. The current paper is written by ESTRO's breast course faculty, providing tricks and tips for target volume definition and delineation for optimal postoperative breast cancer irradiation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Breast cancer; Delineation; ESTRO; Lymph nodes; Radiation therapy

Tumor-Associated Neutrophils Are a Negative Prognostic Factor in Early Luminal Breast Cancers Lacking Immunosuppressive Macrophage Recruitment - Schmidt, Eva; Distel, Luitpold; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie-Charlotte; Ott, Oliver; Strnad, Vratislav; Hack, Carolin; Hartmann, Arndt; Hecht, Markus; Fietkau, Rainer; Schnellhardt, Sören (Cancers, 2024)
Background: Tumor-associated neutrophils (TANs) are important modulators of the tumor microenvironment with opposing functions that can promote and inhibit tumor progression. The prognostic role of TANs in early luminal breast cancer is unclear. Methods: A total of 144 patients were treated for early-stage hormone-receptor-positive breast cancer as part of an Accelerated Partial Breast Irradiation (APBI) phase II trial. Resection samples from multiple locations were processed into tissue microarrays and sections thereof immunohistochemically stained for CD66b+ neutrophils. CD66b+ neutrophil density was measured separately in the stromal and intraepithelial compartment. Results: High stromal and intraepithelial CD66b+ TAN density was a negative prognostic factor in central tumor samples. In addition, neutrophil density in adjacent normal breast tissue and lymph node samples also correlated with reduced disease-free survival. TAN density correlated with CD163+ M2-like tumor-associated macrophage (TAM) density, which we analyzed in a previous study. TANs were a negative prognostic factor in tumors with an elevated M1/M2 TAM ratio, while this impact on patient outcome was lost in tumors with a low M1/M2 ratio. A combined multivariate analysis of TAM and TAN density revealed that only TAM polarization status was an independent prognostic factor. Conclusions: CD66b+ neutrophils were a negative prognostic factor in early-stage luminal breast cancer in single-marker analysis. Combined analysis with TAMs could be necessary to correctly evaluate their prognostic impact in future studies. TAN recruitment might act as a compensatory mechanism of immunoevasion and disease progression in tumors that are unable to sufficiently attract and polarize TAMs.
CRIS-Team Scopus Importer:2024-10-11
Keywords: breast cancer; CD66b; luminal; tumor-associated macrophages; tumor-associated neutrophils

Tumor ENPP1 (CD203a)/Haptoglobin Axis Exploits Myeloid-Derived Suppressor Cells to Promote Post-Radiotherapy Local Recurrence in Breast Cancer - Ruiz-Fernández de Córdoba, Borja; Moreno, Haritz; Valencia, Karmele; Perurena, Naiara; Ruedas, Pablo; Walle, Thomas; Pezonaga-Torres, Alberto; Hinojosa, Juan; Guruceaga, Elisabet; Pineda-Lucena, Antonio; Abengózar-Muela, Marta; Cochonneau, Denis; et al. (Cancer Discovery, 2022)
ABSTRACT: Locoregional failure (LRF) in patients with breast cancer post-surgery and post-irradiation is linked to a dismal prognosis. In a refined new model, we identified ectonucleotide pyrophosphatase/phosphodiesterase 1/CD203a (ENPP1) to be closely associated with LRF. ENPP1hi circulating tumor cells (CTC) contribute to relapse by a self-seeding mechanism. This process requires the infiltration of polymorphonuclear myeloid-derived suppressor cells and neutrophil extracellular trap (NET) formation. Genetic and pharmacologic ENPP1 inhibition or NET blockade extends relapse-free survival. Furthermore, in combination with fractionated irradiation, ENPP1 abrogation obliterates LRF. Mechanistically, ENPP1-generated adenosinergic metabolites enhance haptoglobin (HP) expression. This inflammatory mediator elicits myeloid invasiveness and promotes NET formation. Accordingly, a significant increase in ENPP1 and NET formation is detected in relapsed human breast cancer tumors. Moreover, high ENPP1 or HP levels are associated with poor prognosis. These findings unveil the ENPP1/HP axis as an unanticipated mechanism exploited by tumor cells linking inflammation to immune remodeling favoring local relapse. SIGNIFICANCE: CTC exploit the ENPP1/HP axis to promote local recurrence post-surgery and post-irradiation by subduing myeloid suppressor cells in breast tumors. Blocking this axis impairs tumor engraftment, impedes immunosuppression, and obliterates NET formation, unveiling new opportunities for therapeutic intervention to eradicate local relapse and ameliorate patient survival. This article is highlighted in the In This Issue feature, p. 1171.
CRIS-Team Scopus Importer:2022-05-20

Very accelerated partial breast irradiation in 1 or 2 days: Late toxicity and early oncological outcome of the GEC-ESTRO VAPBI cohort - Hannoun-Levi, Jean Michel; Gimeno Morales, Marta; Gal, Jocelyn; Anchuelo, Javier; Guinot, Jose Luis; Gastanaga, Miren; Meszaros, Norbert; Polgar, Csaba; Strnad, Vratislav; Schiappa, Renaud; Gutierrez, Cristina (Radiotherapy and Oncology, 2024)
Purpose: To analyze late toxicity after very accelerated partial breast irradiation (VAPBI) for low-risk breast cancer. Materials: Methods: In this retrospective, observational, international multicenter study (HDH F20220713143949), patients with low-risk breast cancer underwent lumpectomy + vAPBI (high-dose rate multicatheter interstitial brachytherapy-MIBT). VAPBI was performed with 4(4x6.2 Gy/2d), 3(3x7.45 Gy/2d) or 1 fraction (1x16Gy or 1x18Gy/1d). Primary endpoint was late toxicity. Secondary endpoints were cumulative incidence of breast cancer local relapse (LR) and distant metastatic relapse (DMR) and specific (SS) and overall (OS) survivals. Prognostic factors for late toxicity were analyzed. Results: From 01/2012 to 06/2022, 516 pts with early breast cancer were enrolled. Median follow-up was 44 months [95 %CI 39–46]. Median age was 71 years [40–100]. Median tumor size was 12 mm [1–35]. VAPBI delivered 1, 3 and 4 fractions for 205pts (39.7 %), 167pts (32.4 %) and 144pts (28 %) respectively. 221 late toxicity events were observed in 168pts (32.6 %) (Fibrosis, dyschromia, pain and telangiectasia). Grade 2 and 3 late toxicities were observed in 7.2 and 0.6 % respectively (no G4) with no difference between 1 and ≥ 2 treatment days. CTV > 50 cc (p = 0.007) and V150 > 40 % (p = 0.027) were prognostic factors for G ≥ 2 late toxicity. Four-year cumulative incidence rates of LR and DMR were 2 % [95 %CI 0–3] and 1 % [95 %CI 0–2] respectively. Conclusions: VAPBI based on 1 or ≥ 2 days of MIBT represents an attractive de-escalation of irradiation approach for low-risk breast cancer. Late toxicity profile appears acceptable while early oncological outcome shows encouraging local control. Longer follow-up is warranted in order to confirm these preliminary results.
CRIS-Team Scopus Importer:2024-03-22
Keywords: APBI; Brachytherapy; Breast cancer; De-escalation; Fractionation; Toxicity

With regard to Amraee A et al. Evaluation of normal tissue complications in breast cancer re-irradiation: a meta-analysis study - Hannoun-Levi, Jean Michel; Polgar, Csaba; Strnad, Vratislav; Gutierrez, Cristina (Clinical & Translational Oncology, 2024)
CRIS-Team Scopus Importer:2025-02-04

With Regard to Schwieger L. et al. Intraoperative Radiation Therapy for Early-Stage Breast Cancer. DOI: 101002/jso27814 - Hannoun-Levi, Jean Michel; Polgar, Csaba; Strnad, Vratislav; Gutierrez, Cristina (Journal of Surgical Oncology, 2024)
CRIS-Team Scopus Importer:2025-02-04